Machine learning in clarifying the coupled effects of pore structure and nitrogen density on desalination capacity for capacitive deionization - Hao Kong; Hongshan Wang; Ming Gao; Qi Li; Ran Li; Yuchen Kang; Weilong Xiao; Tianqi Ao; Haiyan Mou; Wenqing Chen (Desalination, 2026)

Pathway-dependent observability of a spring Asian-jet precursor for western North Pacific typhoon activity - Zi-Liang Li; Xiao-Ran Wu (Atmospheric Research, 2026)

Bacterial surface interfaces in food systems: a programmable regulatory layer - Hao-Ran Zhang; Jun Meng; Yun-Peng Hao; Jing-Qian Song; Xiao-Yue Wang; Jing-Yi Yang; Zai-Chen Li; Jun Xi; Chang-He Ding; Tong Li (Trends in Food Science & Technology, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Cyanidin chloride activates mitophagy to delay aging via PINK1/parkin pathway - Zhaotun Hu; Yan Ran; Xiaocong Li; He Zha; Yi Xiao (Food Research International, 2026)

Limited enzymatic hydrolysis-mediated assembly of whey protein isolate nanofibers: Influence of protease type and hydrolysis time on fiber formation and β-carotene delivery - Shudong He; Yanni Wu; Tong Jin; Qiming Li; Tianjiao Niu; Xiaodong Cao; Ran Xiao; Hanju Sun; Walid Elfalleh (Food Chemistry, 2026)

PFDA exposure promotes myocardial aging and fibrosis via hyperactivation of the MTORC1 signaling axis - Xiao Guang Chen; Ze Yu Liao; Yi Zhang; Ran Li (Food and Chemical Toxicology, 2026)

Potassium oxalate-activated bamboo charcoal: a green solution for constructing high-performance capacitive deionization electrodes for nitrate removal - Weilong Xiao; Rencheng Li; Ming Gao; Ran Li; Luwei Miao; Yufeng Da; Yang Bao; Ke Li; Tianqi Ao; Qiulin Yang; Xing Chen; Haiyan Mou; et al. (Desalination, 2026)

Toward integrated CO2 capture and photocatalytic conversion: From catalyst design to reactor engineering - Ziyi Li; Chenxi Ran; Jiao Feng; Jun Zhong; Jiaxin Xie; Yue-Fei Zhang; Xiao Luo; Yu Mao; Zhiwu Liang (Chemical Engineering Journal, 2026)

The role of transcription factor MdGeBP3 in Modulating cold stress tolerance and anthocyanin biosynthesis in apple - Ming-Kun Wang; Ran-Xin Liu; Cong-Yu Xu; Yue-Ning Wang; Xiao-Han Qin; Shan-Shan Li; Ying-Xue Lv; Du Liu; Jie Lu; Xiao-Fei Wang (Journal of Plant Physiology, 2026)

Outdoor light at night, sleep disorder, and atopic diseases among children and adolescents: a cross-sectional study - Si-Han Wu; Le-Bing Wang; Xiao-Fan Lu; Yang-Yang Li; Joachim Heinrich; Lidia Morawska; Steve Hung Lam Yim; Shao Lin; Bin Jalaludin; Yi-Ran Chen; Xiao-Yi Liu; Yuan-Yuan Fan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Soy milk fermented by Bacillus subtilis SP-8-5 and Lactiplantibacillus plantarum 4_3 exhibits sedative-hypnotic ability in vivo - Zhen Liu; Zhao-Ying Zeng; Yu-Jin Li; Bin Zhou; Shi-Yi Sun; Xia Ou; Hua Qi; Chen-Jian Liu; Xiao-Ran Li (Food Research International, 2026)

An assessment of direct steam sterilization on texture, flavor, and native functional proteins retention in yogurt - Julong Liu; Shusen Li; Ziqiang Li; Ran Xiao; Yong Guo; Erna Sun; Qiruonan Shen; Yuejiao Wang; Tingting Wang; Shuang Du; Wentao Zhang; Chenyuan Wang (Food and Bioproducts Processing, 2026)

Residential greenness and incident type 2 diabetes: A large prospective cohort study in China integrating evidence from 17 global cohorts - Jian-Cheng Jiang; Chuan-Jiang He; Ai-Min Xu; Lu Wang; Xiao-Qi Zhu; Bei-Bei Li; Wen Liu; Ya Qiu; Jing-Ran Xu; Min-Hui Li; Zhuo-Hao Wang; Xiao-Guang Zou; et al. (Environmental Research, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Network pharmacology and cell experiments suggest natural algal astaxanthin as an anti-atherosclerotic agent via the PPARγ/NF-κB pathway - Yunmei Yin; Pei Wang; Zhen Zhang; Hongxiang Zhao; Meicong Xiao; Ran Chen; Kun Li; Shiqi Zhou; Rongqing Zhang (Algal Research, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

C10–C12 aromatics dominate ozone and secondary organic aerosol formation potential in emissions from printed circuit board manufacturing - Xiaodie Pang; Wei Song; Weiqiang Yang; Chao Peng; Jianqiang Zeng; Zhou Zhang; Xiao Tian; Hongcheng Lu; Xiangyu Zhang; Ran An; Yang Li; Runcheng Zhu; et al. (Journal of Environmental Sciences, 2026)

The tautomerism induced by the number of hydroxyl groups in COFs and its contribution to thorium adsorption - Shangjie Zhao; Long Chen; Xiaofan Ding; Ke Wang; Jicong Li; Ran Zhang; Jing Zhao; Ke Ma; Jinping Liu; Songtao Xiao (Journal of Environmental Sciences, 2026)

Screening and identification of soybean antioxidant peptides using Fe3O4-Modified carbon fibers - Xiao-Feng Chen; Xiang-Yu Huang; Hao-Ran Liu; Li Ding; Li Wen; Xu-Feng Wang; Zhou Xu; Yun-Hui Cheng; Mao-Long Chen (Food Bioscience, 2026)

Macrophage-targeted dual-responsive hollow mesoporous silica nanosystem for photothermal and immunomodulatory elimination of intracellular MRSA - Qiao Guo; Yongchao Yao; Jipeng Xiao; Xinyu Lu; Yiyuan Pu; Ran Li; Zhuo Zhang; Penghai Tang; Yuchen Jiang; Jianbin Luo (Chemical Engineering Journal, 2026)

Aboveground inputs rather than belowground root drive SOC responses to long term N addition in alpine grassland ecosystems of Qinghai-Tibetan Plateau - Ran Zhang; Hao Shen; Shikui Dong; Qiang Yu; Juejie Yang; Ying Li; Yaoming Li; Jiannan Xiao; Shuai Li; Hui Zuo; Hang Shi; Fengcai He; et al. (Agriculture, Ecosystems & Environment, 2026)

Enhanced dimethylsulfide emissions following eutrophication remediation in a coastal bay: biogeochemical and hydrological controls - Xiao-Ran Li; Jin-Wei Wu; Xiao-Song Zhong; Hao Qiao; Shi-Bo Yan; Feng Xu; Yu-Cheng Jiang; Rui-Te Zhang; Yu-Hao Qiu; Hong-Hai Zhang (Progress in Oceanography, 2026)

Nine previously undescribed immunosuppressive ent-labdane diterpenoids from the roots of Eurysolen gracilis - Lin-Lin Teng; Yan-Chun Liu; Chao-Jiang Xiao; Shu-Xi Jing; De-Sen Li; Ran Xu; Xiao-Nian Li; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Gelator-dependent crystalline network tolerance governs probiotic dispersion stability in oleogels through mechanisms involving rheology and crystallization kinetics - Shuai Chen; Zengliu Song; Ran Qiu; Suqiong Fang; Zhe Li; Ronghai Hu; Yong Cao; Jie Xiao (Food Research International, 2026)

Combined bearing capacity of spudcan considering installation effect in clay - Ye Tian; Jiang Tao Yi; Si Yu Li; Hong Yu Tang; Xiao Han; Jing Nian Ran (Computers and Geotechnics, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

Interference of algal C-phycocyanin in type 2 diabetes: Mechanisms involving MAPK pathway activation and GLUT4 translocation - Hongxiang Zhao; Meicong Xiao; Yunmei Yin; Zhen Zhang; Yunyun Yang; Ran Chen; Kun Li; Pei Wang; Shiqi Zhou; Rongqing Zhang (Algal Research, 2026)

Toxoplasma GRA72 is Involved in Membrane-Associated Functions and Metabolic Homeostasis Revealed by Transcriptomic Analysis - Xin-Sheng Lu; Xing Tian; Jing Li; Chen-Ran Tian; Xing-Quan Zhu; Xiao-Nan Zheng (Acta Parasitologica, 2026)

Dietary bamboo vinegar powder supplementation mitigates the adverse effects of a high-starch diet on growth performance, liver health, and glucose-lipid metabolism in largemouth bass (Micropterus salmoides) - Weibin Lai; Zhangyi Xiao; Ran Yu; Linyi Li; Wenqian Chen; Yuan Gao; Manqi Yang; Liangliang Zhang; Liming Lu; Jianchun Jiang (Frontiers in Marine Science, 2026)
This study explored the potential of bamboo vinegar powder (BVP) to mitigate hepatic injury and metabolic disturbance induced by a high-starch diet in largemouth bass ( Micropterus salmoides ). Fish were distributed into three groups (with three replicates per group) and fed for 56 days with a basal diet (BD), a high-starch diet (CSD), and the BVP-supplemented diet (CSDB, added 2.0 g/kg BVP to the CSD diet), respectively. After the feeding trial, fish in the CSD group exhibited a significant decrease in weight gain rate (WGR) and an increased hepatosomatic index (HSI) ( P < 0.05). Concurrently, hepatic glucose and lipid metabolism of fish in the CSD group were suppressed, leading to the accumulation of hepatic lipids and glycogen, along with histopathological manifestations such as hepatic vacuolation and nuclear shift. Furthermore, immune competence and hepatic antioxidant status were also compromised. However, relative to the CSD group, fish in the CSDB group demonstrated significant improvements in growth performance, immune function, and liver injury. Furthermore, BVP upregulated the expression of nuclear factor erythroid 2-related factor 2 ( nrf2 , a key regulator of antioxidant defense) and downregulated the nuclear factor kappa B ( nf - κb , a central transcription factor in inflammation) ( P < 0.05). More importantly, BVP might improve the metabolism of hepatic glucose and lipid in fish, by suppressing gluconeogenesis and promoting glycolysis to optimize glucose metabolism, as well as by inhibiting lipogenesis and promoting both lipid transport and catabolism to enhance lipid metabolism. Notably, dietary BVP supplementation significantly altered hepatic metabolite profiles, affecting pathways such as alpha-linolenic acid and arachidonic acid metabolism, and increasing the levels of several lipid metabolites, including docosahexaenoic acid and phosphatidylethanolamine species, compared to the CSD group ( P < 0.05). Collectively, these results demonstrated that BVP improved growth performance, liver health, and glucose-lipid metabolism in largemouth bass fed a high-starch diet.

Targeting stable desalination via harnessing in situ oxygen reduction reaction in capacitive deionization - Luwei Miao; Ran Li; Ming Gao; Ke Li; Weilong Xiao; Yang Bao; Haiyan Mou; Qiulin Yang; Wenqing Chen (Chemical Engineering Journal, 2026)

Engineering strategies for the biosynthesis of rare sugars in microbial cell factories - Heming Xu; Ran Lu; Mei-Li Sun; Lu Lin; Kaifeng Wang; Xiao-Jun Ji (World Journal of Microbiology and Biotechnology, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Biodegradable microplastics-induced free-living nitrogen fixation enhancement and diazotrophic community differentiation in soils - Yujuan Han; Peixin Gao; Jiping Song; Yanning Li; Xiao Wang; Ning Yang; Xu Zhao; Bo Liu; Chuankun Zhang; Ran Li; Dan Wen; Ying Teng (Journal of Environmental Management, 2026)

AjFOSL Modulates Cell Cycle-Related Genes Associated with Coelomocyte Regeneration in Apostichopus japonicus Evisceration - Ran Xiao; Yinan Wang; Xiaoli Xu; Jiong Wu; Qiang Li (Fishes, 2026)
Apostichopus japonicus undergoes evisceration in response to adverse environmental stimuli, and its coelomocytes undergo rapid regeneration within 6–24 h to restore innate immune function. FOS, an immediate early gene, regulates cell proliferation and cycle, but its role in A. japonicus coelomocyte regeneration after evisceration is unclear. In this study, AjFOSL from A. japonicus was cloned, which harbors a 609 bp open reading frame (ORF) encoding 202 amino acids (aa) with a conserved bZIP domain and is localized on chromosome 14. It shares 58% homology with FOS from Holothuria leucospilota and Lytechinus pictus. Phylogenetic analysis revealed that AjFOSL clusters closely with FOS from Magallana gigas and Mytilus edulis. Tissue distribution analysis showed that AjFOSL was widely expressed in various tissues, with the highest expression level detected in the tentacles. Temporal expression profiling demonstrated that AjFOSL was significantly upregulated by 1.75-fold at 6 h after evisceration. After AjFOSL knockdown, the peak expression of Cyclin A, Cyclin B, and E2F was delayed and the coelomocyte number was consistently reduced compared with that in the evisceration-only group. The AjFOSL acted as an immediate early response gene and was associated with the regulation of coelomocyte regeneration by modulating the expression of cell cycle-related genes. This study provides novel insights into the molecular associations underlying coelomocyte regeneration and the evolutionary adaptation of FOS genes in echinoderms.

Targeting ACSL4: A potential strategy to alleviate deoxynivalenol-mediated intestinal ferroptosis, oxidative stress, and immunosuppression in Channa argus - Yi-Ran Zhao; Tong-Hao Wang; Ze-Xin Zhao; Xiao-Tian Niu; Hong-Ming Lv; Yan-Bing Li; Yang Cao; Mu-Yang Li (Aquaculture, 2026)

miR-199-3p protects chicken granulosa cells from ferroptosis by targeting ZEB1 and activating Wnt/β-catenin signaling - Jinshan Ran; Wei Huang; Yanli Du; Xiao Wang; Tiao Ning; Jing Li (Theriogenology, 2026)

Intercropping significantly elevates carbon sequestration by mitigating the decline in soil total carbon caused by excessive phosphorus-application - Chuan-Lin Xiao; Ran An; Jiu-Dong Zhang; Yi Xing; Xing-Guo Bao; Rui-Peng Yu; Hans Lambers; Xiang Wang; Long Li (Soil and Tillage Research, 2026)

Risk assessment, resistance monitoring and mechanism of field-evolved resistance to broflanilide in the tobacco cutworm, Spodoptera litura - Xiao Guo; Yilu Tong; Ren Li; Shengran Zhang; Daofeng Zhang; Cheng Qu; Xiaoli Ma; Ran Wang (Pesticide Biochemistry and Physiology, 2026)

MdHMGB15 enhances zinc tolerance by activating multiple metal homeostasis genes in apple - Ran-Xin Liu; Ming-kun Wang; Yue-Ning Wang; Xiao-Han Qin; Ying-Xue Lv; Shan-Shan Li; Du Liu; Cong-Yu Xu; Xiao-Fei Wang (Journal of Hazardous Materials, 2026)

Integrative analysis of DEHP exposure and prostate cancer: Mechanistic insights and predictive modeling - Wen-Cai Zheng; Wen-Tao Xu; Chao-Ran Chen; Fei Lin; Shao-Hao Chen; Xiao-Dong Li; Xiong-Lin Sun; Qing-Shui Zheng; Yong Wei; Xue-Yi Xue; Zhi-Bin Ke; Ning Xu (Environmental Pollution, 2026)

Nonlinear threshold response and erosion-driven pathways of sediment organic carbon to anthropogenic activities in a large lake - Fengwei Ran; Tao Xiao; Zhongwu Li; Shilan Wang; Yinglong Hou; Haipeng Wu; Xiaodong Nie (Anthropocene, 2026)

Breaking the antimicrobial resistance dilemma: marine natural products, a treasure trove for the development of new anti-Staphylococcus aureus drugs - Peng-Jie Li; Liu-Xia Lv; Xi-Zhen Cao; Jian-Yu Liu; Ji-Xiu Gao; Hao-Ran Li; Gulab Said; Dan Chen; Bo Yao; Xin Liu; Mei-Yan Wei; Xiao-Ping Yang; et al. (Marine Life Science & Technology, 2026)
Antimicrobial resistance (AMR) affects multiple fields, including medicine, pharmacy, food safety, and animal husbandry, and poses a major threat to public health and economic development. Staphylococcus aureus has emerged as one of the most critical bacterial pathogens due to its widespread prevalence and significant genetic plasticity. This review outlines currently approved small-molecule drugs for clinical use and their mechanisms in controlling bacterial infections and antimicrobial resistance, highlighting the development of novel agents as an effective strategy to combat AMR. Special emphasis is placed on the antibacterial activity of marine-derived natural products (MNPs) against S. aureus , and a systematic analysis is presented for the first time on the structures, origins, activities, and structure–activity relationships of 1,192 compounds reported in 468 publications from 1977 to 2025. Among these, 36 MNPs exhibited significant activity against both methicillin-sensitive S. aureus and methicillin-resistant S. aureus (MIC ≤ 1 µg/mL). Macrolides and peptides represented the most prevalent structural classes, with compounds displaying potent activity accounting for 24% and 27% of the total active compounds, respectively. Further drug-likeness analysis shows that MNPs have promising therapeutic potential. Among the 160 highly active MNPs, over 80% have suitable lipid-water partition coefficients, and 41% fully meet Lipinski's Rule of Five. Structural analysis reveals tetrahydrofuran, tetrahydropyran, and sugar units as the most common motifs, present in 20, 16, and 14 compounds, respectively. Technologies and strategies to accelerate the development of marine-derived antibacterial drugs are also proposed. This will serve stakeholders across diverse sectors by supporting cross-sectoral coordination to address AMR.

Copper-based drugs inhibit infectious bronchitis virus (IBV) in vitro and in vivo - Lisen Lin; Jiaqi Li; Chao Shang; Dapeng Li; Mingzhe Sun; Gaojie Song; Guangbo Qu; Xiao Li; Ran Zhu; Cuiling Zhang; Qinghao He; Guibin Jiang (Veterinary Microbiology, 2026)

γ-lactam and γ-lactone-containing sesterterpenoids from Colquhounia coccinea var. mollis with immunosuppressive activity - Shu-Xi Jing; Chun-Huan Li; Yan-Chun Liu; Ting-Ting Zhou; Ran Fu; Shi-Hong Luo; Yu Zheng; Xiao-Nian Li; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Recent advances in photocatalytic plastic degradation and upcycling: Catalysts, experiments, and mechanisms - Chenxi Ran; Ziyi Li; Yue-Fei Zhang; Xiao Luo; Zhiwu Liang; Yu Mao (Journal of Environmental Chemical Engineering, 2026)

A multiscale risk operation and decision making model for inter-basin water diversion project under climate variability - Juan Chen; Zhen-ran Zhang; Yi-fan Liang; Xiao-hui Fan; Jian-qing Xie; Zhen Li; Ping-an Zhong (Environmental Research, 2026)

CoAFNet: a correlation modelling and Attention Fusion Network for semantic change detection - Zhenni Li; Mengying Ran; Jingyi Liu; Shiming Hu; Hanquan Zhang; Dong Xiao (International Journal of Remote Sensing, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Shimia fortis sp. nov., Isolated from Marine Sediment - Xiao-Yu Dong; Pei-Ran Lin; Xin-Yun Tan; Jia-Qi Li; Zong-Jun Du; Meng-Qi Ye (Current Microbiology, 2026)

Preliminary design and analysis of a radar system model based-on a phased-array RF astro-receiver for space debris detection and tracking - Lalida Tantiparimongkol; Ming Shen; Peng-qi Gao; Xiao-zhong Guo; Huan-huan Yu; Jia-wei Li; Jia-lang Ding; Yu-ting Chu; Ran Duan; You Zhao (Advances in Space Research, 2026)

Resistance mechanisms and fitness outcomes of tetraniliprole, one novel diamide insecticide, in a near-isogenic strain of Spodoptera litura (Lepidoptera: Noctuidae) - Peng Lu; Ren Li; Xiao Guo; Juan Tang; Yilu Tong; Shengran Zhang; Qi Su; Cheng Qu; Ran Wang (Pesticide Biochemistry and Physiology, 2026)

Consolidated combined V-H-M-T capacity of a suction caisson in clay - Hao Ran Li; Xiu Zhe Wang; Jiang Tao Yi; Hong Yu Tang; Xiao Han (Ocean Engineering, 2026)

CD33 Isoform Splicing Dysregulation: A Molecular Determinant of Microglial Dysfunction in Alzheimer’s Disease Pathology - Xiao-Yan Li; Yu Zhang; Zhao Ran; Jia-Xin Luo; Xiao-Qin Yu; Mei-Hong Lu (Molecular Neurobiology, 2026)

High-performance and fast fiber-optic SPR gas sensor based on WO3/SnO2 nanocomposites films for room-temperature NH3 detection - Chong Li; Yan Wang; Jinqiao Hou; Huanming Wang; Jingting Luo; Chen Fu; Fujian Ren; Jikai Zhang; Huiling Ong; Chenze Lu; Hang Xiao; Xi Chen; et al. (Journal of Environmental Chemical Engineering, 2025)

Unveiling the efficacy of a novel strain of Beauveria brongniartii to manage Sitobion miscanthi (Takahashi) and Rhopalosiphum padi (Linnaeus) (Hemiptera: Aphididae) in China - Xujun Tian; Saige Zhu; Xiao Ran; Xinan Li; Xiangrui Li; Yunhui Zhang; Rongyu Li; Xun Zhu (Journal of Asia-Pacific Entomology, 2025)

Floc-granule microbial symbiosis drives DNRA in anammox bacteria via cross-feeding for complete autotrophic nitrogen removal - Yulong Yang; Wen-Bo Nie; Xin Tan; Lili Li; Chenhui Yu; Shibo Fu; Ke-Di Peng; Yi Luo; Xiao Ran; Zhihong Zheng; Jin Xu; Jun Li; et al. (Chemical Engineering Journal, 2025)

Targeted-nanoformulation of cannabidiol attenuates endothelial injury and platelet hyperactivation for combating silicosis - Sirong Chang; Yue Sun; Wenyue Zhang; Yi Guo; Huning Zhang; Nan Li; Ran An; Mengsi Xiao; Siwei Zou; Na Zhang; Kai Wang; Anning Yang; et al. (Chemical Engineering Journal, 2025)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

Genome-Wide Identification and Expression Profiling of Oryza Sativa Sulfotransferase Genes Associated with Oxyfluorfen and Fluroxypyr-Meptyl Metabolism - Li Qing Zeng; Xiao Yu Zhong; Nian Hua Teng; Xu Zhen Shi; Yi Zhuo Wang; Xi Ran Cheng; Ying Yu Zeng; Zhao Jie Chen (Tropical Plant Biology, 2025)

Identification, Characterization, and Expression Profiling of Oryza Sativa Betaine Aldehyde Dehydrogenase Genes Exposed to Realistic Environmental Contamination of Oxyfluorfen - Yi Zhuo Wang; Jun Jin Lu; Xu Zhen Shi; Ya Nan Qu; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Yan Hui Wang; Zhao Jie Chen (Tropical Plant Biology, 2025)

Correction to: Unveiling the potential of bio-organic fertilizers to enhance crop yield and improve soil and microbial environments: A meta-analysis in China - Xiaofang Huang; Wei Sun; Chengqun Yu; Peili Shi; Junxi Wu; Fadong Li; Ran Xiao; Jialuo Yu; Jiabao Wang; Tao Mu (Plant and Soil, 2025)

The NLRP3 inflammasome: a pivotal orchestrator of multisystem diseases—from molecular mechanisms to therapeutic innovation - Shu-yan Xiao; Ya-hui Lv; Yin-min Ji; Yi Dong; Mei-cen Liu; Tao Li; Xiao-ran Cui; Yi Hu (Molecular Biology Reports, 2025)

Development of novel melatonin-isatin hybrids as multifunctional agents for Alzheimer’s disease - Ying-Ying Zhong; Jun‑Ze Deng; Qin Wang; Li Chen; Zi-Hang Yang; Ya-Mei Zhang; Lu‑Yi Zhou; Yi-Ran Li; Jia-Qiang Wu; Xiao-Qin Wang (Molecular Diversity, 2025)

Identification, characterization, and expression profiling of putrescine synthesis genes associated with bentazone metabolism in Oryza sativa - Li Qing Zeng; Nian Hua Teng; Ying Yu Zeng; Zhi Jiang He; Yi Zhuo Wang; Zhi Zhong Zhou; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetic Resources and Crop Evolution, 2025)

Identification, characterization, and expression profiling of rice MADS-box transcription factor genes associated with fluroxypyr-meptyl and oxyfluorfen metabolism - Zhi Zhong Zhou; Nian Hua Teng; Jia Lin Liang; Ying Yu Zeng; Yi Zhuo Wang; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetica, 2025)

A three-step process for purification and stability evaluation of analytical-grade phycocyanin from Spirulina - Hongxiang Zhao; Shilin Wu; Zhen Zhang; Ran Chen; Kun Li; Meicong Xiao; Yunmei Yin; Pei Wang; Rongqing Zhang (Algal Research, 2025)

Large-scale single tree information extraction of oil palm in Malaysia based on sub-meter visible light satellite images - Sen Zhang; Nan Li; Yaoping Cui; Jinwei Dong; Le Yu; Lishan Ran; Ziyue Chen; Jiqiang Niu; Wei Yan; Kasturi Devi Kanniah; Xiangming Xiao (Computers and Electronics in Agriculture, 2025)

Regulation of phytoplankton community by mesoscale eddies and the East Indian Coastal Current in the southwestern Bay of Bengal during the northeast monsoon - Hao Chen; Yuanli Zhu; Lihua Ran; Mengjia Zhang; Xiao Ma; Hongliang Li; Feng Zhou; W.N.C. Priyadarshani; Zhibing Jiang (Marine Environmental Research, 2025)

“One stone, two birds”: A one-step sustainable dual-salt template route to synthesize glucose-derived porous carbon towards ammonium ion removal via capacitive deionization - Luwei Miao; Ming Gao; Ran Li; Ke Li; Weilong Xiao; Rencheng Li; Tianqi Ao; Yunjia Ling; Haiyan Mou; Wenqing Chen (Desalination, 2025)

Unveiling the potential of bio-organic fertilizers to enhance crop yield and improve soil and microbial environments: A meta-analysis in China - Xiaofang Huang; Wei Sun; Chengqun Yu; Peili Shi; Junxi Wu; Fadong Li; Ran Xiao; Jialuo Yu; Jiabao Wang; Tao Mu (Plant and Soil, 2025)

A new flavonostilbene glycoside and four new stilbene derivatives from the roots of Polygonum multiflorum - Shuo-Guo Li; Zheng-Ran Zou; Xiao-Feng Zheng; Yue Sun; Shu-Mei Wang (Natural Product Research, 2025)

Latest progress based on doped-TiO2 photocatalysis materials: Fabrication and applications - Xiao-Ni Qi; Ya-Qi Zhu; Hui Yuan; Zi-Xuan Xu; Hao-Ran Guo; Zhen-Liang Li (Journal of Water Process Engineering, 2025)

Enzymatic and Non-Enzymatic decolorization of synthetic dyes using spent mushroom substrate - Wenjing Xiao; Ya Ran; Xinyu Guo; Yujun Dai; Zhilin Zhang; Jiashu Liu; Changchun Li (World Journal of Microbiology and Biotechnology, 2025)

Grazing mediates soil nutrient stocks through changing the plant functional composition and plant biomass allocation in alpine grassland - Fengcai He; Shikui Dong; Chunhui Ma; Xinghai Hao; Hao Shen; Juejie Yang; Jiannan Xiao; Yu Li; Ran Zhang; Hang Shi; Ziying Wang; Yuhao Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Effect of anticyclonic eddies on the production and emission of marine dimethylsulfide in the northern South China Sea - Jin-Wei Wu; Feng Xu; Shi-Bo Yan; Gao-Bin Xu; Yu-Cheng Jiang; Xiao-Ran Li; Xing Zhai; Li-Min Zhou; Hong-Hai Zhang; Zhao-Hui Chen (Global and Planetary Change, 2025)

Enhancing bioavailability and functionality of plant peptides and proteins: A review of novel strategies for food and pharmaceutical applications - Salumu Masuwa Shadrack; Yezhi Wang; Shichao Mi; Ran Lu; Yutong Zhu; Zheng Tang; David Julian McClements; Chongjiang Cao; Xiao Xu; Wenjun Li; Biao Yuan (Food Chemistry, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Deciphering the physiological response mechanisms of Miscanthus sinensis to salt-induced stress - Hai-Long Lu; Ling Li; Jackson Nkoh Nkoh; Jian-Jian Li; Hao-Ran Wang; Xiao-Hui Li; Dong-Li Hao; Jun-Qin Zong (Biomass and Bioenergy, 2025)

Effects of nitrogen deposition on temporal stability and resistance of the alpine steppe plant communities on the Qinghai-Tibetan Plateau - Ran Zhang; Hao Shen; Shikui Dong; Qiang Yu; Bing Zhang; Jiannan Xiao; Shuai Li; Hui Zuo; Hang Shi; Fengcai He; Ke Zhang; Yuhao Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Rotational grazing can enhance the soil available nutrients rather than plant diversity to promote ANPP of alpine steppe - Fengcai He; Shikui Dong; Juejie Yang; Xinghai Hao; Chunhui Ma; Hao Shen; Jiannan Xiao; Yu Li; Ran Zhang; Hang Shi; Ziying Wang; Yuhao Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Influence of UHT processing and storage on the gastrointestinal fate and bioavailability of bovine milk proteins - Xing Li; Xiuxiu Zhang; Ran Xiao; Tianjiao Niu; Yuxiang Gu (Food Bioscience, 2025)

Rock moisture dynamics in sandstone caves responsible for weathering: Field observations and numerical modeling - Ran Niu; Xiao-Wei Jiang; Kaigao Ouyang; Xi Yang; Xu-Sheng Wang; Ji-Zhong Huang; Hong-Bing Yan; Li Wan (Engineering Geology, 2025)

Machine learning-based prediction of desalination capacity of electrochemical performance of nitrogen-doped for capacitive deionization - Hao Kong; Ming Gao; Ran Li; Luwei Miao; Yuchen Kang; Weilong Xiao; Wenqing Chen; Tianqi Ao; Haiyan Mou (Desalination, 2025)

Air pollution of PM2.5-bound PAHs in urban Chongqing, China from 2015 to 2022: Concentration, source tracking and health risk - Bofei Fu; Shang Li; Shushu Lan; Xiaowei Peng; Chongjun Ran; Nanyan Li; Hong Li; Lun Xiao; Guohua Zhao; Junrui Chang; Jingxiu Han; Yunyun Wu; et al. (Urban Climate, 2025)

α-Pyrones, root growth inhibitors from a mesophotic zone sponge-associated fungus Purpureocillium sp. NBUF263 - Yu-Ying Liu; Ting-Ting Wei; Guang-Jun Ran; Xiao-Hui Li; Salman Khan; Tao Cai; Chan-Ting Lai; Hong-Kun Wang; Bin Wu; Hai-Xiao Jin; Wei-Yan Zhang; Ting-Ting Wang; et al. (Phytochemistry Letters, 2025)

Impact of ultrasonication on the regeneration of tetracycline-saturated activated carbon and activated coke using persulfate - Xiao Mi; Dongyang Ren; Guobiao He; Yuming Cui; Gangfu Song; Baogui Wang; Yingxu Liu; Yunlong Ran; Tannaz Pak; Guoting Li (Journal of Environmental Chemical Engineering, 2025)

Schistosoma japonicum cystatin attenuated CLP-induced sepsis in mice though inducing tolerogenic dendritic cells and regulatory T cells - Yi-Xiang Wang; Yi-Dan Ma; Hui-Hui Li; Wen-Juan Duo; Qi-Wang Jin; Kai-Jun Zhou; Yan-Ran Gao; Jun-Nan He; Yu-Jie Xie; Liang Chu; Xiao-Di Yang (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

Short-term P addition weakens the positive effects of N addition on CH4 uptake in alpine grasslands of the Qinghai-Tibetan Plateau - Jiannan Xiao; Shikui Dong; Hao Shen; Ran Zhang; Hang Shi; Fencai He; Wei Li; Xiaoyan Li (Plant and Soil, 2025)

Isolation and identification of a novel bisacodyl analogue, bisacodyl dicycloproyl carboxylate, as a potential illegal additive in a dried plum product advertised for weight loss - Xian-Xian Li; Feng Jiang; Hong Yu; Xiao-Jing Huang; Jing-Xian Zhang; Jin-Tao Xia; Ying-ying Ran; Fan Huang; Jian Sun; Qing Hu (Food Additives & Contaminants: Part A, 2025)

Virtual screening and characterization of novel myogenic peptides from bovine collagen hydrolysates: Targeting myomaker - Hanfeng Li; Yunci Wang; Xiao Yong Ran; Qi Hao; Jianing Wang; Bing Zhang; Yanchuan Guo (Food Research International, 2025)

The mechanisms of salt weathering responsible for sandstone deterioration in the Yungang Grottoes, China - Xi Yang; Xiao-Wei Jiang; Kai-Gao Ouyang; Tao-Tao Ji; Yi-Fan Gao; Xiao-Hong Geng; Ran Niu; Ji-Zhong Huang; Hong-Bing Yan; Li Wan (Engineering Geology, 2025)

Response of bacterial community structure in saline soils to the application of kitchen waste-derived fermented organic fertilizer - Bin Xie; Wenzhuo Li; Tao Yang; Yajun Zhang; Weidong Xiao; Sihai Hu; Yaoguo Wu; Xiaofeng Sun; Bin wang; Ran Sun (World Journal of Microbiology and Biotechnology, 2025)

Endophytic fungi promote peanut fitness by re-establishing rhizosphere nematode communities under continuous monocropping conditions - Xiang-Yu Zhang; Hao-Ran Li; Hui-Jun Jiang; Xiao-Han Wu; Chen-Yu Ma; De-Lin Luo; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

High urea promotes mitochondrial fission and functional impairments in astrocytes inducing anxiety-like behavior in chronic kidney disease mice - Xi Zhao; Shengyao Zhang; Mengna Wu; Binyun Zhang; Guoran Wan; Meng Zhang; Jing Li; Zhuo Fei; Guoqi Zhu; Shaoqiu Jiang; Mohan Xiao; Wanjia Liu; et al. (Metabolic Brain Disease, 2025)

Socioeconomic developments drove regime shifts of agriculture–ecology–economy nexus of social-ecological system: Four-decade lessons from southeast China - Xinhua Li; Chong Jiang; Yixin Wang; Xiaohuang Liu; Jie Liu; Jun Wang; Ying Zhao; Yuexin Xiao; Zhiyuan Yang; Ran Wang (Journal of Environmental Management, 2025)

Sand Production and Critical Rate in Stress-Sensitive Unconsolidated Sandstone: An Experimental Study - Xiao-Hua Tan; Rui Wang; Xiao-Jun Zhou; Yao Zhu; Cai-Shen Li; Bo Cao; Zhi Yang; Hao Chen; Bao-Quan Wen; Liu Tang; Huan-Yu Ran (Geotechnical and Geological Engineering, 2025)

Application of extreme gradient boosting for predicting standard penetration test N-values from cone penetration test data - Xiao Han; Jiangtao Yi; Xiaobin Li; Siyu Li; Hongyu Tang; Zhen Wang; Jingnian Ran (Bulletin of Engineering Geology and the Environment, 2025)

Paleoceanographic and paleoenvironmental changes in the high-latitude Southern Ocean during late Quaternary: progress and prospects based on the Chinese Antarctic Expeditions - Li Wu; Rujian Wang; Wenshen Xiao; Qingmiao Li; Kaitao Ni; Ran Xu; Yi Chen (Acta Oceanologica Sinica, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Chronic intermittent hypoxia modulates energy metabolic pathways and improves hypoxia tolerance capacity in golden pompano, Trachinotus blochii - Geng Hui Fang; Xiao Li Zhou; Chun Li Ran; Chun Xiu Jin; Shao Yang Bu; Yue Chen; Yong Gong; Zeng Tan Hu; Fei Biao Song; Jian Luo; Jun Long Sun (Science of The Total Environment, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

FSD1 inhibits glioblastoma diffuse infiltration through restriction of HDAC6-mediated microtubule deacetylation - Dake Xiao; Haowen Ran; Lishu Chen; Yuanyuan Li; Yan Cai; Songyang Zhang; Qinghui Qi; Huiran Wu; Cheng Zhang; Shuailiang Cao; Lanjuan Mi; Haohao Huang; et al. (Science China Life Sciences, 2025)
The infiltration of glioblastoma multiforme (GBM) is predominantly characterized by diffuse spread, contributing significantly to therapy resistance and recurrence of GBM. In this study, we reveal that microtubule deacetylation, mediated through the downregulation of fibronectin type III and SPRY domain-containing 1 (FSD1), plays a pivotal role in promoting GBM diffuse infiltration. FSD1 directly interacts with histone deacetylase 6 (HDAC6) at its second catalytic domain, thereby impeding its deacetylase activity on α-tubulin and preventing microtubule deacetylation and depolymerization. This inhibitory interaction is disrupted upon phosphorylation of FSD1 at its Ser317 and Ser324 residues by activated CDK5, leading to FSD1 dissociation from microtubules and facilitating HDAC6-mediated α-tubulin deacetylation. Furthermore, increased expression of FSD1 or interference with FSD1 phosphorylation reduces microtubule deacetylation, suppresses invasion of GBM stem cells, and ultimately mitigates tumor infiltration in orthotopic GBM xenografts. Importantly, GBM tissues exhibit diminished levels of FSD1 expression, correlating with microtubule deacetylation and unfavorable clinical outcomes in GBM patients. These findings elucidate the mechanistic involvement of microtubule deacetylation in driving GBM cell invasion and offer potential avenues for managing GBM infiltration.

Discovery, optimization and biological evaluation of chromone derivatives as novel BRD4 inhibitors - Zhao-Tong Jia; You Li; Wei Shi; Jian-Qiang Qian; Ya-Yu Xu; Hai-Ran Fan; Xiao-Long Hu; Hao Wang (Medicinal Chemistry Research, 2025)

Cxcl9 modulates aging associated microvascular metabolic and angiogenic dysfunctions in subcutaneous adipose tissue - Xin Fu; Yu Zhao; Xiwei Cui; Siyuan Huang; Yanze Lv; Chen Li; Fuxing Gong; Zhigang Yang; Xiaonan Yang; Ran Xiao (Angiogenesis, 2025)

Biochar enhanced co-composting for peat-free seedling substrate: A win-win solution for sustainable development of modern vegetable industry - Xiaoxia Fan; Yiyuan Wei; Dan Song; Ting Zhou; Ronghua Li; Xiaoxuan Su; Tao Zhang; Shang Cheng; Ran Xiao (Process Safety and Environmental Protection, 2025)

A novel framework for dynamic and quantitative mapping of damage severity due to compound Drought–Heatwave impacts on tea Plantations, integrating Sentinel-2 and UAV images - Ran Huang; Yuanjun Xiao; Shengcheng Li; Jianing Li; Wei Weng; Qi Shao; Jingcheng Zhang; Yao Zhang; Lingbo Yang; Chao Huang; Weiwei Sun; Weiwei Liu; et al. (Computers and Electronics in Agriculture, 2025)

Corrigendum to “Chitosan/rutin multifunctional hydrogel with tunable adhesion, anti-inflammatory and antibacterial properties for skin wound healing” [Carbohydr. Polym. 343 (2024) 122492 - Ran An; Chenyu Shi; Yan Tang; Zan Cui; Yinping Li; Zhiyong Chen; Min Xiao; Li Xu (Carbohydrate Polymers, 2025)

Co-hydrothermal carbonization of lignocellulosic biomass and swine manure: Optimal parameters for enhanced nutrient reclamation, carbon sequestration, and heavy metals passivation - Weijie Xiong; Yuping Luo; Wengao Shangguan; Yue Deng; Ronghua Li; Dan Song; Muyuan Zhang; Zengyi Li; Ran Xiao (Waste Management, 2024)

Biodegradation of imidacloprid and diuron by Simplicillium sp. QHSH-33 - Ke Xu; Xin-Ran Ke; Wan-Ting Zhang; Xin-Yuan Wu; Zhi-Jun Song; Mei-Juan Jiao; Xiao-Juan Gao; Li Zhou; Hong-Yan Ji; Fang Wang; Xiu-Li Wu (Pesticide Biochemistry and Physiology, 2024)

Construction of Bi5O7I/Bi3O4Br heterojunction with abundant oxygen vacancies to enhance photocatalytic performance - Jian Feng; Xia Ran; Li Wang; Bo Xiao; Keqin Zhang; Jinming Zhu; Zuoji Liu; Chaozhong Li; Xinai Cui; Rong Li; Guangwei Feng (Journal of Environmental Chemical Engineering, 2024)

Environmental Persistent Free Radicals in highly polluted soils and the association with polycyclic aromatic compounds - Yongqiang Zhang; Yousong Zhou; Hanchen Wang; Kai Xiao; Zhihan Luo; Yaojie Li; Ran Xing; Ke Jiang; Donglei Fu; Wenxin Liu; Shu Tao; Guofeng Shen (Environmental Research, 2024)

Fractions of smoke leakage into indoor space from residential solid fuel combustion in chimney stoves - Zhihan Luo; Tianyao Huang; Yatai Men; Ran Xing; Yaojie Li; Ke Jiang; Kai Xiao; Guofeng Shen (Environmental Pollution, 2024)

Effects of oyster shell addition on shrimp aquaculture and the dynamic succession of surface biofilm microbial communities - Xianke Huang; Guoqiang Xiao; Xiang Zhang; Shuangshuang Teng; Min Li; Yilong Cai; Ran Chen; Xiaolin Huang (Frontiers in Marine Science, 2024)
Introduction In the context of Litopenaeus vannamei aquaculture, the incorporation of oyster shells has proven beneficial for enhancing water quality and the growth conditions of the shrimp. Nonetheless, the specific effects of in-situ water treatment using oyster shells on water quality and shrimp growth, along with the composition and succession dynamics of the microbial community within oyster shell biofilms, have yet to be thoroughly investigated. Methods This study established control, low-concentration, and high-concentration oyster shell addition groups to emulate the in-situ water treatment environment with oyster shells, with the objective of elucidating the impacts of oyster shell addition on the aquaculture setting. Results The results showed that the addition of oyster shells could significantly improve the length ( F = 12.248, P = 0.005 ), weight( F = 138.234, P < 0.001 ), and survival rate ( F = 15.248, P < 0.001 ) of shrimp, while there were no significant differences in the length ( F = -1.233, P = 0.267 ) and survival rate ( F = -2.143, P = 0.076 ) between the high and low concentration groups. Additionally, oyster shell addition resulted in elevated phosphate levels ( F = 74.92, P < 0.001 in Day 70), diminished nitrite levels ( F = 5.276, P = 0.031 in Day 56), and increased nitrate concentrations ( F = 9.421, P = 0.006 in Day 70). Within the biofilms, the relative abundances of Ruegeria, Tenacibaculum , BD2- 11_terrestrial_group , and Kapabacteriales exhibited significant declines over time, whereas the relative abundance of Nitrospira demonstrated a marked increase, ultimately emerging as the predominant bacterium (Relative abundance 31.8%) in the biofilms during the latter stages of the experiment. Nitrospira also exhibited a notably higher relative abundance in the microbial community of the experimental water group relative to the control group ( F = 2.265, P = 0.001 ). Discussion The biofilm provided conditions for the proliferation of Nitrospira , thereby accelerating the transformation of nitrite into nitrate in the aquaculture system, which subsequently improved the shrimp farming conditions. This research offers valuable insights for the application of oyster shells in shrimp farming and contributes to the theoretical underpinnings necessary for advancing our understanding of the mechanisms through which oyster shell biofilms enhance water quality and foster shrimp health.

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Boosting bioelectricity generation in bioelectrochemical systems with nitrogen-doped three-dimensional graphene aerogel anode - Yi-Xuan Wang; Xiao-Li Liu; Wen-Qiang Li; Yi-Ran Wang; Ke-Wan Li; Zhi-Cheng Pan; Yang Mu (Water Research, 2024)

Different responses of individuals, functional groups and plant communities in CSR strategies to nitrogen deposition in high-altitude grasslands - Xueqi Li; Ying Li; Hao Shen; Shuai Li; Zhenzhen Zhao; Jiannan Xiao; Ran Zhang; Hang Shi; Hui Zuo; Tu Danjia; Guoming Chen; Xueli Zhou; et al. (Science of The Total Environment, 2024)

Optimized ammonium-nitrate ratios in constructed wetlands for simultaneously efficient nitrogen removal and greenhouse gas reduction - Ling-Min Zhang; Ran Liu; Xiao-Qin Luo; Ying Liu; Xi-Qi Li; Qing-Jie Meng; Hong-Cheng Wang (Journal of Water Process Engineering, 2024)

Chitosan/rutin multifunctional hydrogel with tunable adhesion, anti-inflammatory and antibacterial properties for skin wound healing - Ran An; Chenyu Shi; Yan Tang; Zan Cui; Yinping Li; Zhiyong Chen; Min Xiao; Li Xu (Carbohydrate Polymers, 2024)

Gigantic gastropods from the Middle Triassic Qingyan biota of Guizhou - Xin Sun; Li Tian; Chuan-Yuan Liu; Xiao He; Dao-Liang Chu; Xue Miao; Shi-Yan Zhang; Yi-Ran Cao; Pei-Shan Li; Jin-Nan Tong; Hai-Jun Song (Palaeoworld, 2024)

Contribution to energy conservation and quality improvement of frozen pork via contact/contactless immersion freezing in NaCl solution - Yu Zhou; Xia Yu; Ran Xiao; Li-fang Zou; Qing-fei Du; Fei Ma; Cong-gui Chen (Meat Science, 2024)

Effect of pasteurization and storage on the bioavailability of milk proteins during in vitro intestinal digestion and Caco-2 cell transport - Xing Li; Ran Xiao; Shudong He; Yuxiang Gu; Tianjiao Niu (Food Bioscience, 2024)

Progress toward adsorption mechanism exploration method for capacitive deionization: Experimental, mathematical model, computational chemistry and machine learning - Luwei Miao; Ming Gao; Weilong Xiao; Yuchen Kang; Ran Li; Hao Kong; Haiyan Mou; Wenqing Chen; Tianqi Ao (Desalination, 2024)

Enhanced humification attributed by the integration of Fenton reagent and oxalic acid during a co-composting of swine manure and corn straw: Impacts and the possible mechanisms - Minna Jiao; Feixue Yue; Xiuna Ren; Xiangyu Zhan; Wanying Xu; Daniel Kuok Ho Tang; Ran Xiao; Ronghua Li (Chemical Engineering Journal, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

A data-knowledge joint-driven reinforcement learning algorithm based on guided policy and state-prediction for satellite continuous-thrust tracking - Xiao Wang; Jiake Li; Lu Cao; Dechao Ran; Mingjiang Ji; Kewu Sun; Yuying Han; Zhe Ma (Advances in Space Research, 2024)

B/N modified carbon nanofiber mesh covered with layered double hydroxide for large current overall water splitting - Ji Qi; Chunqi Zhu; Jianing Hu; Shuai Ran; Tauqeer Ahmad; Siraj Ullah; Lixu Chen; Yi Chen; Yuqing Xia; Xue Sun; Chuang Li; Xiao Chen; et al. (Fuel, 2024)

Exogenous sulfur application can effectively alleviate iron deficiency yellowing in peanuts and increase pod yield - Xiao-yan Zhang; Wen-feng Hou; Ze-chang Gou; Shu-ran Jia; Han Li; Qiang Gao; Xiao-yu Li (European Journal of Agronomy, 2024)

Fibroblast growth factor receptor 4 deficiency in macrophages aggravates experimental colitis by promoting M1-polarization - Luyao Shen; Cong Wang; Ran Ren; Xudong Liu; Dongqin Zhou; Yu Chen; Yu Zhou; Juan Lei; Yang Xiao; Nan Zhang; Huakan Zhao; Yongsheng Li (Inflammation Research, 2024)

Moving forward from escaping the poverty trap in China's greenest regions: Examining four decades of socioecological evolution to re-orient sustainable development policies - Xinhua Li; Chong Jiang; Yixin Wang; Jie Liu; Ran Wang; Ying Zhao; Jie Zhang; Haiyan Zhang; Buqing Wang; Yuexin Xiao (Applied Geography, 2024)

Multi-GNSS broadcast ephemeris errors assessment and weight determination of different constellations for SPP - Hang Shen; Ran Li; Shuhui Li; Jingbin Liu; Xiao Chen; Jiajia Xu (Advances in Space Research, 2024)

Porous carbon prepared by thermal dissolution of coal and biomass for high-performance supercapacitors - Yi Liu; Wei-Dong Cao; Xing Fan; Ran-Ran Hou; Xiang Bai; Xiao-Yun Zhang; Yan Li; Guo-Ming Zhao; Peng Liang (Fuel, 2024)

Occurrence and mechanism of sulfamethoxazole in alginate-like extracellular polymers from excess sludge - Chen Shi; Ming Cheng; Run-Gen Zeng; Cong-Cong Li; Qian Wang; Li-Ting Hao; Ran-Bin Liu; Xiao-Di Hao; Xiang-Yang Wang; Yuan-Yuan Wu (Bioresource Technology, 2024)

The protective effect and mechanism of piperazine ferulate in rats with 5/6 nephrectomy-caused chronic kidney disease - Xiu-Meng Zhang; Xin-Ran Min; Dan Li; Bo Li; Yi-Xin rui; Hong-Xiao Xie; Rong Liu; Nan Zeng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Experimental evidence that nitrogen-fixing cyanobacterium Trichodesmium spp. supplies new nitrogen source to marine phytoplankton - Shuang-Qing Li; Yan Xiao; Hai-Long Huang; Zhen Luo; Tao-Ran Sun; Hua-Yang Gao; Xin-Wei Wang; Hai-Bo Jiang (Frontiers in Marine Science, 2024)
In oligotrophic oceans, primary productivity is widely limited by nitrogen bioavailability. The broadly distributed and abundant nitrogen-fixing cyanobacterium Trichodesmium plays an important role in the oceanic nitrogen and carbon cycles by providing a “new” source of nitrogen to many non-diazotrophic microbes, thereby driving new primary production in the ocean. However, the underlying process and mechanism of nitrogen supply from Trichodesmium to other phytoplankton remain unclear. Here, our results demonstrated that the fixed nitrogen released by Trichodesmium could sustain the growth of a non-nitrogen-fixing cyanobacterium Synechococcus sp. PCC 7002, including a mutant strain (Mut- ureA ) that cannot use urea. However, the growth rate of Mut- ureA was approximately 20% lower than that of the wild strain when Trichodesmium filtrate was used for nitrogen supply. This result was consistent with the composition of the Trichodesmium exudate, in which urea comprised more than 20% of the total fixed nitrogen that was released. It is evident from the experiments that a fraction of the Trichodesmium -derived nitrogen was not available to Mut- ureA . Our results suggested that Trichodesmium produces dissolved organic nitrogen, especially a certain amount of urea as a “new” nitrogen source, benefiting in particular populations of surrounding phytoplankton species.

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Reducing carbon and nitrogen loss by shortening the composting duration based on seed germination index (SCD@GI): Feasibilities and challenges - Ran Xiao; Lan Li; Yanye Zhang; Linfa Fang; Ronghua Li; Dan Song; Tao Liang; Xiaoxuan Su (Science of The Total Environment, 2024)

Evolution of reservoir quality related to clay coating overgrowths in tight sandstone in the fluvial facies of the southeastern Sichuan Basin - Xiao Dong; Bo Ran; Zhiwu Li; Zijian Wang; Huan Xu; Yebo Wang (Marine and Petroleum Geology, 2024)

The fabrication of Mn single atoms/clusters on Al2O3 for enhanced catalytic NO oxidation - Xiao-Ke Hou; Hui-Xin Zhang; Yi-Bo Wang; Jin-Ping Zhang; Xin Gao; Lei Chen; Chao Li; Hong-Mei Jing; Chi He; Qiang Lu; Chun-Ran Chang (Fuel, 2024)

Mechanical protein polycystin-1 directly regulates osteoclastogenesis and bone resorption - Mei Huang; Jingxuan Zhou; Xiaoxiao Li; Ran Liu; Yangzi Jiang; Kaixuan Chen; Yurui Jiao; Xin Yin; Ling Liu; Yuchen Sun; Weishan Wang; Ye Xiao; et al. (Science Bulletin, 2024)

Promoting effect of polyoxometallic acid modification on the NH3-SCR performance of Mn-based catalysts - Yi Dong; Mingchu Ran; Xiao Zhang; Saisai Lin; Weixian Li; Yang Yang; Hao Song; Weihong Wu; Shaojun Liu; Chenghang Zheng; Xiang Gao (Journal of Environmental Chemical Engineering, 2024)

Associations between exposure to phthalates and liver function among women undergoing assisted reproductive technology - Yi Wang; Li Yin; Yao-Yao Du; Hong-Mei Liao; Juan Li; Wen Yao; Xiao-Qiong Yuan; Qing-Chun Guo; Tao-Ran Deng; Na Guo; Min Zhang; Qiang Zeng; et al. (Environmental Toxicology and Pharmacology, 2024)

Coupled effects of human activities and river–Lake interactions evolution alter sources and fate of sedimentary organic carbon in a typical river–Lake system - Shilan Wang; Fengwei Ran; Zhongwu Li; Changrong Yang; Tao Xiao; Yaojun Liu; Xiaodong Nie (Water Research, 2024)

Spatial modelling of street-level carbon emissions with multi-source open data: A case study of Guangzhou - Yingsheng Zheng; Wenjie Li; Lu Jiang; Chao Yuan; Te Xiao; Ran Wang; Meng Cai; Haobin Hong (Urban Climate, 2024)

Methyl benzoate-related compounds as potential repellents and fumigants for the control of cigarette beetle, Lasioderma serricorne (F.) - Junli Xiao; Jianbo Jin; Shanyi Chen; Jianfeng Zhang; Peijian Cao; Li-Juan Mao; Ran Li (Journal of Stored Products Research, 2024)

Preferentially in-situ generated copper nanograins boosting fast kinetic conversion magnesium storage of bimetallic copper-cobalt sulfide cathode - Yaping Xia; Chunxiao Chen; Lin Ran; Hou-an Zhang; Shuai Cui; Panfei Xiao; Fei Xu; Daohong Zhang; Ting Li (Chemical Engineering Journal, 2024)

Lightning activity and microphysical structure characteristics during the convective cell mergers in an extreme mesoscale convective system - Jing Sun; Yanjiao Xiao; Yunying Li; Muyun Du; Zhikang Fu; Liang Leng; Ran Cai; Haopeng Wu (Atmospheric Research, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Curvularin derivatives from the marine mangrove derived fungus Penicillium sumatrense MA-325 - Yi-Ran Wang; Yu-Liang Dong; Xiao-Ming Li; Xiao-Shan Shi; Hong-Lei Li; Ling-Hong Meng; Rui Xu; Bin-Gui Wang (Phytochemistry, 2024)

Promoting nitrogen conversion in aerobic biotransformation of swine slurry with the co-application of manganese sulfate and biochar - Xuan Wu; Xinyu Zhao; Guorong Yi; Wanqiang Zhang; Runyu Gao; Daniel Kuok Ho Tang; Ran Xiao; Zengqiang Zhang; Yiqing Yao; Ronghua Li (Journal of Environmental Management, 2024)

A novel p-type CoSe2 co-catalyst cooperated with hematite for boosting photoelectrochemical water splitting - Shanshan Jiang; Dabo Liu; Dongke Li; Mengyuan Xiao; Yunchou Deng; Yu Han; Ran Tao; Xiaoxing Fan; Kuiyong Liu (Fuel, 2024)

A novel Zr-P-modified nanomagnetic herbal biochar immobilized Cd and Pb in water and soil and enhanced the relative abundance of metal-resistant bacteria: Biogeochemical and spectroscopic investigations to identify the governing factors and potential mechanisms - Yueru Fang; Ping Wang; Lan Zhang; Han Zhang; Ran Xiao; Yuan Luo; Kuok Ho Daniel Tang; Ronghua Li; Hamada Abdelrahman; Zengqiang Zhang; Jörg Rinklebe; Sang Soo Lee; et al. (Chemical Engineering Journal, 2024)

Construction of dual functional CuAl-LDHs nanocomposite loaded with IGF2BP3 siRNA for enhanced therapy of gastric cancer - Haiping Li; Yuying Zhang; Bo Huang; Feifei Yang; Qiang Ma; Xiaolin Wang; Yuying Liu; Junwu Ren; Xiaojuan Pan; Ce Liang; Shimin Wang; Hao Ning; et al. (Chemical Engineering Journal, 2024)

Triblock polymer PDMAEMA-co-PNIPAM-co-PMPC to deliver siKRAS for gene therapy in pancreatic cancer - Lidong Cao; Mengmeng Dong; Kai Jiang; Qing Zhu; Feng Li; Zunqiang Xiao; Hao Tang; Ran Tao (Chemical Engineering Journal, 2024)

Tricarboxylic acid cycle metabolites: new players in macrophage - Ying Yang; Bing-Bing Cui; Jian Li; Jiao-Jiao Shan; Jun Xu; Cheng-Yong Zhang; Xiao-Tong Wei; Ri-Ran Zhu; Jing-Yi Wang (Inflammation Research, 2024)

Driver–response relationships in a large shallow lake since the Anthropocene: Short‐term abrupt perturbations versus long‐term sustainable pressures - Fengwei Ran; Shilan Wang; Xiaodong Nie; Tao Xiao; Changrong Yang; Yaojun Liu; Zhongwu Li (Global Change Biology, 2024)
Lakes, as integral social‐ecological systems, are hotspots for exploring climatic and anthropogenic impacts, with crucial pathways revealed by continuous sediment records. However, the response of multi‐proxies in large shallow lakes to typical abrupt events and sustained drivers since the Anthropocene remains unclear. Here, we explored the driver‐identification relationships between multi‐proxy peaks and natural and anthropogenic events as well as the attribution of short‐term perturbations and long‐term pressures. To this end, sediment core records, socio‐ecological data, and documented events from official records were integrated into a large shallow lake (Dongting Lake, China). Significant causal cascades and path effects (goodness‐of‐fit: 0.488; total effect: −1.10; p .001) were observed among catchment environmental proxies, lake biogenic proxies, and mixed‐source proxies. The peak‐event identification rate (PEIR) and event‐peak driving rate were proposed, and values of 28.57%–46.43% and 50%–81.25% were obtained, respectively. The incomplete accuracy of depicting event perturbations using sediment proxies was caused by various information filters both inside and outside the lake. PEIRs for compound events were 1.41 (±0.72) and 1.09 (±0.46) times greater than those for anthropogenic‐dominated and natural‐dominated events, respectively. Furthermore, socio‐economic activity, hydrologic dynamics, land‐use changes, and agriculture exerted significant and persistent pressures, cumulatively contributing 55.3%–80.9% to alterations in sediment proxies. Relatively synergistic or antagonistic trends in temporal contributions of these forces were observed after 2000, which were primarily attributed to the “Grain for Green” project and the Three Gorges Dam. This study represents one of the few investigations to distinguish the driver–response relationship of multiple proxies in large shallow lakes under typical event perturbations and long‐term sustained pressures since the Anthropocene. The findings will help policymakers and managers address ecological perturbations triggered by climate change and human activities over long‐term periods.

Micro formation mechanism of oil–water inversion in reservoirs based on water film theory—An example from the Dawangzhuang Oilfield in Bohai Bay Basin - Xiao Hu; Longchuan Pu; Aihua Ran; Jun Xie; Fengqun Li; Yuzong Cheng; Suhua Zhang; Zhe Li; Qiongyao Pu; Jialin Fu (Fuel, 2024)

Tumor microenvironment-activated hollow vanadium-based nanoplatform for precise therapy of lung cancer through synergistically reversing cisplatin resistance - Lang Ran; Jianmin Xiao; Weijie Zhang; Miaomiao Wang; Huan Xin; Huimin Li; Hong Hao; Maoyang Wang; Xiaofei Wang; Geng Tian; Guilong Zhang (Chemical Engineering Journal, 2024)

Storage, form, and influencing factors of karst inorganic carbon in a carbonate area in China - Chaochao Du; Xiaoyong Bai; Yangbing Li; Qiu Tan; Cuiwei Zhao; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Sirui Zhang; Lian Xiong; et al. (Science China Earth Sciences, 2024)

Leucine improves dietary protein use efficiency by regulating protein synthesis by activating amino acid transporters and the mTORC1 pathways in Chinese mitten crab (Eriocheir sinensis) - Ming-Qi Song; Qiu-Ran Yu; Er-Chao Li; Ying Song; Xin-Yu Cai; Yu-Xiang Huang; Chuan-Jie Qin; Xiao-Dan Wang; Jian-Guang Qin; Li-Qiao Chen (Aquaculture, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Production of carbon nanotubes via catalytic pyrolysis of polyethylene over Ni/ZSM-5 prepared by ethylene glycol assisted impregnation - Qing-Lin Li; Rui Shan; Shu-Xiao Wang; Tao-li Huhe; Hao-Ran Yuan; Yong Chen (Fuel, 2024)

A new cyclohexenone derivative from phomopsis sp. XM-01 - Cheng-Yao Wang; Dong Gan; Chen-Zhe Li; Li Zhu; Xiao-Ran Zhang; Ya-Ni Li; Xiu-Hong Wu; Hao Zhou; Le Cai (Natural Product Research, 2024)

Grain-size, coarse fraction lithology and clay mineral compositions of surface sediments from Ross Sea, Antarctica: implications for their provenance and delivery mode - Li Wu; Longwei Li; Rujian Wang; Hebin Shao; Yi Chen; Zipei Lin; Yue Liu; Wenshen Xiao; Ran Xu (Frontiers in Marine Science, 2024)
Knowledge on spatial distribution, provenance and delivery mode of surface sediment aids in interpretation of nearby sediment records for paleoenvironmental reconstruction. Such knowledge, however, remains largely unknown for the modern Ross Sea, Antarctica: a key region for understanding the dynamical behavior of Antarctic Ice Sheet over geological past. In this study, we address this gap by analyzing the grain-size distribution, coarse fraction (>250 μm) lithology, and clay mineralogy of a set of surface sediment samples covering the whole Ross Sea continental shelf. Our data reveals that the sediments were mostly delivered by icebergs and bottom currents. Iceberg delivery was significantly controlled by factors such as water depth, proximity to the iceberg sources, and invasion of the Modified Circumpolar Deep Water. Bottom current activity was stronger in the Western Ross Sea (WRS) than in the Eastern Ross Sea (ERS), controlled by the formation and transport of Dense Shelf Water. Three major sorts of coarse fraction were identified, including the quartz-rich Iceberg Rafted Detritus (IRD) originating from West Antarctic glaciers and primarily distributed in the ERS, the mafic rocks-rich IRD from the Ferrar Group as well as the McMurdo Volcanic Group and mainly found in the WRS, and deformed silt traced back to the grounding zone of the David Glacier-Dragalski Ice Tongue system. The distribution of clay minerals is dominated by a distinct binary mixing pattern. Smectite and kaolinite are mainly present in the ERS, derived from beneath the West Antarctic Ice Sheet. Higher illite and chlorite contents were found offshore of the Southern Victoria Land, derived from the East Antarctic craton. Overall, these results demonstrate that the glaciers draining into Ross Sea from both the East and West Antarctic Ice Sheets are highly dynamical in the context of modern climate conditions, with implications for potential contribution to future sea level rise.

Unveiling the crucial role of soil microorganisms in carbon cycling: A review - Haowei Wu; Huiling Cui; Chenxi Fu; Ran Li; Fengyuan Qi; Zhelun Liu; Guang Yang; Keqing Xiao; Min Qiao (Science of The Total Environment, 2024)

Dryness stress weakens the sustainability of global vegetation cooling - Zilin Li; Xiaoyong Bai; Qiu Tan; Cuiwei Zhao; Yangbing Li; Guangjie Luo; Fei Chen; Chaojun Li; Chen Ran; Sirui Zhang; Lian Xiong; Fengjiao Song; et al. (Science of The Total Environment, 2024)

Differences in background environment and fertilization method mediate plant response to nitrogen fertilization in alpine grasslands on the Qinghai-Tibetan Plateau - Shun He; Jianqing Du; Yanfen Wang; Lizhen Cui; Wenjing Liu; Yifan Xiao; Qinwei Ran; Linfeng Li; Zuopei Zhang; Li Tang; Ronghai Hu; Yanbin Hao; et al. (Science of The Total Environment, 2024)

Occurrence, distribution, and ecological risk of heavy metals and veterinary antibiotics in soils from citrus orchards: side effects of organic substitution - Pingping Ye; Kunpeng Gao; Hua Feng; Linfa Fang; Dong Li; Jong-Hwan Park; Yueqiang Zhang; Ran Xiao (Journal of Soils and Sediments, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Csswin-unet: a Swin-unet network for semantic segmentation of remote sensing images by aggregating contextual information and extracting spatial information - Dong Xiao; Zhihao Kang; Yanhua Fu; Zhenni Li; Mengying Ran (International Journal of Remote Sensing, 2023)

Livestock grazing may weaken N deposition effects on soil C:N:P stoichiometry in alpine grassland of the Qinghai-Tibetan Plateau - Hao Shen; Shikui Dong; Shuai Li; Hanzhong Zheng; Qiyun Wang; Junxiang Liu; Jiannan Xiao; Hui Zuo; Ran Zhang; Xiuchun Yang (CATENA, 2023)

Inter-laboratory validation by event-specific qPCR methods for the detection of genetically modified insect and herbicide-tolerant maize DBN9501 - Jing Wang; Bing Xiao; Ruiying Zhang; Haitao Guan; Yang Yang; Yijia Ding; Ran Yuan; Xiaolei Zhang; Lingyan Li; Jingang Liang; Hongtao Wen (Journal of Consumer Protection and Food Safety, 2023)

Kilogram-scale synthesis of carbon dots with high-efficiency full-color solid-state fluorescence using an aggregation-induced emission strategy - Hui Ding; Ran Zhao; Zi-Hui Zhang; Jia-Jia Yang; Zheng Wang; Lu-Lan Xiao; Xue-Hua Li; Xin-Jian He; Huan-Ming Xiong (Chemical Engineering Journal, 2023)

In-situ introduction of CePO4 for stabilizing electrocatalytic activity of quasi-MOF with partially missing C≡N skeleton - Shuke Li; Meng Xie; Xiao Zhang; Nana Wang; Ran Wang; Yanchao Xu; Hongjun Lin; Yang Jiao; Jianrong Chen (Chemical Engineering Journal, 2023)

Sulfur-aided aerobic biostabilization of swine manure and sawdust mixture: Humification and carbon loss - Yang Wang; Jingwen Wang; Guorong Yi; Xuan Wu; Xiu Zhang; Xu Yang; Kuok Ho Daniel Tang; Ran Xiao; Zengqiang Zhang; Guangzhou Qu; Ronghua Li (Bioresource Technology, 2023)

Enzymatic DNA repairing amplification-powered construction of an Au nanoparticle-based nanosensor for single-molecule monitoring of cytosine deaminase activity in cancer cells - Wen-jing Liu; Rui Song; Xiao-ran Zou; Dong-ling Li; Qinfeng Xu; Chun-yang Zhang (Analytica Chimica Acta, 2023)

Spring photosynthetic phenology of Chinese vegetation in response to climate change and its impact on net primary productivity - Yingying Xue; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Yangbing Li; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Sirui Zhang; Min Liu; et al. (Agricultural and Forest Meteorology, 2023)

Efficient activation of persulfate by metallic sulfide mineral for the efficient removal of pesticides: Performance, radical generation and mechanism - Xie Chen; Wen-Xuan Zhang; Zhi-Liang Chen; Xiao-Wen Yao; Man-Li Chen; Lin-Yin Tong; Wei Qian; Peng-Ran Guo; Ling-Jun Kong; Zeng-Hui Diao (Journal of Cleaner Production, 2023)

Enhanced retention of surface-adsorbed atomic hydrogen through sulfidation of nano zerovalent iron for water decontamination - Guan-Nan Zhou; Jia-Qi Chen; Wen-Qiang Li; Chuan-Shu He; Li Gong; Xiao-Cheng Liu; Yi-Ran Wang; Dahong Huang; Yang Mu (Chemical Engineering Journal, 2023)

Design of a novel chimeric peptide via dual blockade of CD47/SIRPα and PD-1/PD-L1 for cancer immunotherapy - Zheng Hu; Wanqiong Li; Shaomeng Chen; Danhong Chen; Ran Xu; Danlu Zheng; Xin Yang; Shuzhen Li; Xiuman Zhou; Xiaoshuang Niu; Youmei Xiao; Zhuoying He; et al. (Science China Life Sciences, 2023)

Global prevalence and factors affecting the level of Cryptosporidium contamination in soil: A systematic review, meta-analysis, and meta-regression - Mu-Ran Zuo; Xiao-Ting Li; Rui-Zhe Xu; Wen-Chao Sun; Hany M. Elsheikha; Wei Cong (Science of The Total Environment, 2023)

Spatial variability of arsenic fractionation in an abandoned arsenic-containing mine: Insights into soil particle sizes and quantitative mineralogical analysis - Hongzhen Ran; Zhaohui Guo; Liwen Yi; Xiyuan Xiao; Rui Xu; Zhihao Hu; Tianshuang Li (Science of The Total Environment, 2023)

Optimization of runner and vane blade angle of an oscillating water column based on genetic algorithm and neural network - Jiahao Lu; Fangfang Zhang; Ran Tao; Xiaoqin Li; Di Zhu; Ruofu Xiao (Ocean Engineering, 2023)

A novel bacteriocin RSQ01 with antibacterial activity and its application and metabolomic mechanism in milk preservation - Yan-Mei Zhang; Lin-Yu Yang; Jian-Ping Ying; Chao-Min Fu; Gang Wu; Xiao-Ran Li; Qi-Lin Zhang (Food Control, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

Synergetic effect and mechanism of elementary sulphur, MgSO4 and KH2PO4 progressive reinforcement on pig manure composting nitrogen retention - Yang Wang; Jingwen Wang; Xuan Wu; Ran Zhao; Zengqiang Zhang; Juanjuan Zhu; Muhammad Azeem; Ran Xiao; Junting Pan; Xiu Zhang; Ronghua Li (Environmental Pollution, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

A significant loop of lake sedimentation state links catchment eco‐surroundings and lake biogenic regime shifts - Fengwei Ran; Xiaodong Nie; Shilan Wang; Tao Xiao; Changrong Yang; Yi Liu; Lingxia Wang; Yaojun Liu; Xin Chu; Zhongwu Li (Limnology and Oceanography, 2023)
As an important destination for upstream materials and element accumulation, lake sediments hold a multitude of contextual information about climatic changes and anthropogenic disturbances. However, understanding the lake sedimentation state to link catchment pressures and biogenic regime shifts remains challenging. To address this, research was conducted on the lake sedimentation state, including the dynamics, catchment drivers, effects on biogenic regimes, and responses to typical historical events using nine sediment cores from Dongting Lake, China, a typical global priority ecoregion. Three transitions of lake sedimentation state were distinguished over the century (1937, 1968, and 1993), whereby hydrologic dynamics and land‐use changes in the watershed were the direct drivers with relative contributions of 16.30% and 14.56%, respectively. Lake sedimentation state and organic matter inputs not only preceded sediment biogenic elements at the shift time but also exhibited nonlinear trigger effects on biogenic element contents ( R 2 = 0.47, p

Microbial community composition and cooccurrence patterns driven by co-contamination of arsenic and antimony in antimony-mining area - Wei-song Pan; Qi Zou; Min Hu; Wai-chin Li; Xiao-ran Xiong; Yan-ting Qi; Chuan Wu (Journal of Hazardous Materials, 2023)

Carbon nanotubes production from catalytic pyrolysis of polyethylene over nickel-based catalysts: The influence of support materials - Qing-Lin Li; Rui Shan; Shu-Xiao Wang; Hao-Ran Yuan; Yong Chen (Fuel, 2023)

Intraspecific variations of adaptive strategies of native and invasive plant species along an elevational gradient - Hasigerili; Kun Guo; Miao-Miao Zheng; Rui-Ling Liu; Yan-Yan Wang; Yuan Gao; Li Shu; Xiao-Ran Wang; Jian Zhang; Wen-Yong Guo (Flora, 2023)

Terrigenous organic carbon contributes to reservoir carbon emissions: Potential role of the microbial community along a trophic gradient - Qiong Tang; Lunhui Lu; Fang Luo; Xinrui Li; Yuanyuan Zhang; Ran Li; Carolina Bernal; Solange Vera; Irina Izaguirre; Yan Xiao; Zhe Li (Journal of Hydrology, 2023)

Ag@Bi5O7I nanoparticles deposited on Bi(OH)3 nanosheets for boosting photocatalytic antibacterial activity under visible light irradiation - Qinghan Chen; Li Wang; Dehui He; Bo Xiao; Xia Ran; Rong Li; Hong Xu; Jian Feng (Journal of Environmental Chemical Engineering, 2023)

Convergence and divergence emerging in climatic controls of polynomial trends for northern ecosystem productivity over 2000–2018 - Wenxin Zhang; Hongxiao Jin; Sadegh Jamali; Zheng Duan; Mousong Wu; Youhua Ran; Jonas Ardö; Lars Eklundh; Anna Maria Jönsson; Huaiwei Sun; Guojie Hu; Xiaodong Wu; et al. (Science of The Total Environment, 2023)

Yellow Petal locus GaYP promotes flavonol biosynthesis and yellow coloration in petals of Asiatic cotton (Gossypium arboreum) - Yaohua Li; Lingfang Ran; Tong Mo; Nian Liu; Jianyan Zeng; Aimin Liang; Chuannan Wang; Qingwei Suo; Zhong Chen; Yi Wang; Nianjuan Fang; Shijia Xu; et al. (Theoretical and Applied Genetics, 2023)

A systematic analysis and evaluation of nutritional composition of 23 strains of marine microalgae commonly used in aquaculture - Jia-Xing Zhang; Zhao-Shou Ran; Hai-Xuan Xie; Fei Kong; Meng-Qi Zhang; Yao Zhou; Yan-Rong Li; Kai Liao; Xiao-Jun Yan; Ji-Lin Xu (Algal Research, 2023)

Two new chemical constituents from the leaves of Illicium dunnianum - Jun-Ran Shao; Sen-Ju Ma; Ting Li; Xiao-Qing He; Zhen-Zhong Wang; Wei Xiao; Xin-Sheng Yao; Hai-Bo Li; Yang Yu (Natural Product Research, 2023)

A new cyclopentenone derivative from Trichoderma atroviride HH-01 - Li Zhu; Jia-Peng Wang; Feng Hao; Dong Gan; Xiao-Ran Zhang; Chen-Zhe Li; Cheng-Yao Wang; Liang Zhang; Le Cai (Natural Product Research, 2023)

Anthropogenic activities control the source dynamics of sediment organic carbon in the lower reach of an inland river - Changrong Yang; Zhongwu Li; Shilan Wang; Fengwei Ran; Xiaodong Nie; Yaojun Liu; Tao Xiao (Water Research, 2023)

Study of vortex rope for the flow field pulsation law - Faye Jin; Puxi Li; Ran Tao; Ruofu Xiao; Di Zhu (Ocean Engineering, 2023)

The eradication of biofilm for therapy of bacterial infected chronic wound based on pH-responsive micelle of antimicrobial peptide derived biodegradable microneedle patch - Xiao-Ling Lei; Kai Cheng; Yong Li; Zi-Tao Zhong; Xiao-Lin Hou; Lai-Bo Song; Fang Zhang; Jian-Hao Wang; Yuan-Di Zhao; Qiu-Ran Xu (Chemical Engineering Journal, 2023)

Fast asteroidal period inversion by parallel acceleration-based three-step reduced voting - Yong-Xiong Zhang; Xiao-Ping Lu; Tan Guo; Xin-Ran Li (Advances in Space Research, 2023)

Interleukin-17D mediates Vibrio harveyi infection-related changes in Tegillarca granosa though activation of activator protein 1 in vivo - Qiujin Wang; Guoqiang Xiao; Gaoyu Hu; Ran Chen; Min Li; Shuangshuang Teng (Aquaculture, 2023)

Insights into carbon loss reduction during aerobic composting of organic solid waste: A meta-analysis and comprehensive literature review - Pingping Ye; Linfa Fang; Dan Song; Muyuan Zhang; Ronghua Li; Mukesh Kumar Awasthi; Zengqiang Zhang; Ran Xiao; Xinping Chen (Science of The Total Environment, 2023)

Enhanced production of sugars and UV-shielded lignin/PAN fiber mats from chemi-mechanical pulps - Lei Wang; Xiaohan Li; Chenzhong Wan; Kesheng Zhang; Zhao Wu; Fen Hu; Ran Zhang; Xiao Fu; Hongbo Yu (Science of The Total Environment, 2023)

Dietary pattern interfered with the impacts of pesticide exposure by regulating the bioavailability and gut microbiota - Ai Song Chen; Dong Hui Liu; Hao Nan Hou; Jia Ning Yao; Shou Chun Xiao; Xiao Ran Ma; Pei Ze Li; Qian Cao; Xue Ke Liu; Zhi Qiang Zhou; Peng Wang (Science of The Total Environment, 2023)

Responses of carbon and water use efficiencies to climate and land use changes in China's karst areas - Biqin Xiao; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Yangbing Li; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Xuling Luo; Huipeng Xi; et al. (Journal of Hydrology, 2023)

Efficient electrocatalytic reduction of CO2 to CO on highly dispersed Ag nanoparticles confined by Poly(ionic liquid) - Guo-Yi Duan; Xiao-Qiang Li; Yi-Ran Du; Bao-Hua Xu (Chemical Engineering Journal, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

Azospirillum Endophyticum sp. nov., an Endophyte of Paris Polyphylla Smith var. Yunnanensis - Peng-Chao Zhan; Rui-Feng Mao; Cong-Jian Li; Zhen Zhang; Jing-Ran Liu; Mei Tang; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2023)

The roles of ETS transcription factors in liver fibrosis - Li-Ye Zhang; Yong Tan; Xiao-Jie Luo; Jiang-Feng Wu; Yi-Ran Ni (Human Cell, 2022)

New polymerized sesquiterpene lactones from Ainsliaea yunnanensis and their activity evaluation - Na Zhou; Jin-Jie Li; Yong Wu; Ze-Yu Wang; Xin Wang; Zhi-Peng Yin; Xin-Peng Wang; Yi-Ran Liu; Xiao-Ya Shang (Natural Product Research, 2022)

Neuropeptide FF-related gene in fish (Larimichthys polyactis): identification, characterization, and potential anti-inflammatory function - Ran Xiao; Zuting Guo; Li-bing Zheng; Wei Huang; Chang-feng Chi; Bao Lou (Molecular Biology Reports, 2022)

Identification of a major stable QTL for spikelet number in wheat (Triticum aestivum L.) and its genetic effects analysis on yield-related traits - Mingsu Cao; Jizi Dong; Hao Wang; Yibiao Cai; Tianhang Ma; Xiaohan Zhou; Jingguo Xiao; Shihui Li; Linqu Chen; Huiyuan Xu; Chunhua Zhao; Yongzhen Wu; et al. (Euphytica, 2022)

High‐resolution mapping of the global silicate weathering carbon sink and its long‐term changes - Chaojun Li; Xiaoyong Bai; Qiu Tan; Guangjie Luo; Luhua Wu; Fei Chen; Huipeng Xi; Xuling Luo; Chen Ran; Huan Chen; Sirui Zhang; Min Liu; et al. (Global Change Biology, 2022)
Climatic and non‐climatic factors affect the chemical weathering of silicate rocks, which in turn affects the CO 2 concentration in the atmosphere on a long‐term scale. However, the coupling effects of these factors prevent us from clearly understanding of the global weathering carbon sink of silicate rocks. Here, using the improved first‐order model with correlated factors and non‐parametric methods, we produced spatiotemporal data sets (0.25° × 0.25°) of the global silicate weathering carbon‐sink flux (SCSF α ) under different scenarios (SSPs) in present (1950–2014) and future (2015–2100) periods based on the Global River Chemistry Database and CMIP6 data sets. Then, we analyzed and identified the key regions in space where climatic and non‐climatic factors affect the SCSF α . We found that the total SCSF α was 155.80 ± 90 Tg C yr −1 in present period, which was expected to increase by 18.90 ± 11 Tg C yr −1 (12.13%) by the end of this century. Although the SCSF α in more than half of the world was showing an upward trend, about 43% of the regions were still showing a clear downward trend, especially under the SSP2‐4.5 scenario. Among the main factors related to this, the relative contribution rate of runoff to the global SCSF α was close to 1/3 (32.11%), and the main control regions of runoff and precipitation factors in space accounted for about 49% of the area. There was a significant negative partial correlation between leaf area index and silicate weathering carbon sink flux due to the difference between the vegetation types. We have emphasized quantitative analysis the sensitivity of SCSF α to critical factors on a spatial grid scale, which is valuable for understanding the role of silicate chemical weathering in the global carbon cycle.

Testing the isotopic equilibrium fractionation on active speleothem based on cave monitoring - Yang-Yang Huang; Ting-Yong Li; Chao-Jun Chen; Ran Huang; Tao Wang; Yao Wu; Si-Ya Xiao; Yu-Zhen Xu; Hai-Ying Qiu; Yan Yang; Jun-Yun Li (Journal of Earth System Science, 2022)

Janibacter endophyticus sp. nov., an Endophytic Actinobacterium Isolated from the Root of Paris polyphylla Smith var. Yunnanensis - Zhen Zhang; En-Min Zhou; Cong-Jian Li; Xing-Wang Jiang; Rui-Feng Mao; Jing-Ran Liu; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2022)

Neobacillus paridis sp. nov., an endophyte of Paris polyphylla Smith var. yunnanensis - Peng-Chao Zhan; Cong-Jian Li; Zhen Zhang; Rui-Feng Mao; Jing-Ran Liu; Xing-Wang Jiang; Xiao-Yang Zhi; Ling-Ling Yang (Archives of Microbiology, 2022)

Genome resequencing-based high-density genetic map and QTL detection for yield and fiber quality traits in diploid Asiatic cotton (Gossypium arboreum) - Yaohua Li; Tong Mo; Lingfang Ran; Jianyan Zeng; Chuannan Wang; Aimin Liang; Yonglu Dai; Yiping Wu; Ziman Zhong; Yuehua Xiao (Molecular Genetics and Genomics, 2022)

Editing arcs to improve the capacity of GNSS-IR for soil moisture retrieval in undulating terrains - Qishun Ran; Bao Zhang; Yibin Yao; Xiao Yan; Junyu Li (GPS Solutions, 2022)

Human activity and climate change triggered the expansion of rocky desertification in the karst areas of Southwestern China - Chaojun Chen; Daoxian Yuan; Hai Cheng; Tsailuen Yu; Chuanchou Shen; R. Lawrence Edwards; Yao Wu; Siya Xiao; Jian Zhang; Tao Wang; Ran Huang; Ziqi Liu; et al. (Science China Earth Sciences, 2021)

Association of Circulating ICAM3 Concentrations with Severity and Short-term Outcomes of Acute Ischemic Stroke - Hu Zicheng; Yang Xiao; Huang Rongzhong; Li Yongyong; Ran Haitao; Shang Tingting (Neurotoxicity Research, 2021)

KCNQ Channels in the Mesolimbic Reward Circuit Regulate Nociception in Chronic Pain in Mice - Hao-Ran Wang; Su-Wan Hu; Song Zhang; Yu Song; Xiao-Yi Wang; Lei Wang; Yang-Yang Li; Yu-Mei Yu; He Liu; Di Liu; Hai-Lei Ding; Jun-Li Cao (Neuroscience Bulletin, 2021)
Mesocorticolimbic dopaminergic (DA) neurons have been implicated in regulating nociception in chronic pain, yet the mechanisms are barely understood. Here, we found that chronic constructive injury (CCI) in mice increased the firing activity and decreased the KCNQ channel-mediated M-currents in ventral tegmental area (VTA) DA neurons projecting to the nucleus accumbens (NAc). Chemogenetic inhibition of the VTA-to-NAc DA neurons alleviated CCI-induced thermal nociception. Opposite changes in the firing activity and M-currents were recorded in VTA DA neurons projecting to the medial prefrontal cortex (mPFC) but did not affect nociception. In addition, intra-VTA injection of retigabine, a KCNQ opener, while reversing the changes of the VTA-to-NAc DA neurons, alleviated CCI-induced nociception, and this was abolished by injecting exogenous BDNF into the NAc. Taken together, these findings highlight a vital role of KCNQ channel-mediated modulation of mesolimbic DA activity in regulating thermal nociception in the chronic pain state.

Biotransformation of Phlorizin by Eurotium cristatum to Increase the Antioxidant and Antibacterial Activity of Docynia indica Leaves - Jie Xie; Jiang Chen; Xue-ran Mei; Ming-jun Zhu; Xue-li Li; Juan Du; Xiao-yu Zhang (Current Microbiology, 2021)

Transcriptome sequencing and analysis for the pigmentation of scale and skin in common carp (Cyprinus carpio) - Yu-Jie Zhao; Jun Xiao; Mei-Di Huangyang; Ran Zhao; Qi Wang; Yan Zhang; Jiong-Tang Li (Molecular Biology Reports, 2021)

miR-19a mitigates hypoxia/reoxygenation-induced injury by depressing CCL20 and inactivating MAPK pathway in human embryonic cardiomyocytes - Qiang Fu; Tao-Ran Mo; Xiao-Yang Hu; Yin Fu; Ji Li (Biotechnology Letters, 2021)

Characterization of phosphorus engineered biochar and its impact on immobilization of Cd and Pb from smelting contaminated soils - Jing Ren; Zixuan Zhao; Amjad Ali; Weidou Guan; Ran Xiao; Jim J. Wang; Sirui Ma; Di Guo; Baoyue Zhou; Zengqiang Zhang; Ronghua Li (Journal of Soils and Sediments, 2020)

Grenville-age orogenic event along the northeastern margin of the Quanji massif, NW China: constraints from ~1.1 Ga migmatite - Zhouxuan Xiao; Licheng Ma; Wan Jiang; Ran Wang; Yuyan Yao; Jie Cai; Jingyu Lin; Lu Li (Geosciences Journal, 2020)

Species richness and biodiversity significance of alpine micro-waterbody systems in Gaoligong Mountain, Northwest Yunnan, China - Shuo-Ran Liu; Davide Fornacca; Dao-De Yang; Lu Tan; Xian-Fu Li; Guo-Peng Ren; Jun Sun; Xiao-Yang He; Wen-Shu Yang; Qing-Hua Cai; Wen Xiao (Journal of Mountain Science, 2020)

Juxtaposed membranes underpin cellular adhesion and display unilateral cell division of multicellular magnetotactic prokaryotes - Xin‐Xin Qian; Claire‐Lise Santini; Artemis Kosta; Nicolas Menguy; Hugo Le Guenno; Wenyan Zhang; Jinhua Li; Yi‐Ran Chen; Jia Liu; François Alberto; Leon Espinosa; Tian Xiao; et al. (Environmental Microbiology, 2020)
Summary Multicellular magnetotactic prokaryotes (MMPs) exhibit peculiar coordination of swimming along geomagnetic field lines. Approximately 40–80 cells assemble, with a helical geometry or axisymmetry, into spherical or ellipsoidal MMPs respectively. To contribute to a comprehensive understanding of bacterial multicellularity here we took multiple microscopic approaches to study the diversity, assembly, reproduction and motility of ellipsoidal MMPs. Using correlative fluorescence in situ hybridization and scanning electron microscopy analysis, we found an unexpected diversity in populations of ellipsoidal MMPs in the Mediterranean Sea. The high‐pressure freezing/freeze substitution fixation technique allowed us to show, for the first time, that cells adhere via juxtaposed membranes and are held together by a rimming lattice. Fluorescence confocal microscopy and ultrathin section images revealed not only the one‐layer hollow three‐dimensional architecture, but also periphery–core unilateral constriction of constituent cells and unidirectional binary fission of the ellipsoidal MMPs. This finding suggests the evolution toward MMPs multicellularity via the mechanism of incomplete separation of offspring. Remarkably, thousands of flagellar at the periphery surface of cells underpin the coordinated swimming of MMPs in response to mechanical, chemical, magnetic and optical stimuli, including a magnetotactic photokinesis behaviour. Together these results unveil the unique structure and function property of ellipsoidal MMPs.

Enhanced removal of phosphate and ammonium by MgO-biochar composites with NH3·H2O hydrolysis pretreatment - Ran Xiao; Han Zhang; Zhineng Tu; Ronghua Li; Songling Li; Zhongyang Xu; Zengqiang Zhang (Environmental Science and Pollution Research, 2020)

Geochemistry and sedimentology of the Upper Ordovician–lower Silurian black shale in the northern margin of the Upper Yangtze Platform, South China: implications for depositional controls on organic-matter accumulation - B. Xiao; S. G. Liu; B. Ran; Z. W. Li (Australian Journal of Earth Sciences, 2020)

Population genetic structure of Thryssa kammalensis in the Chinese Seas inferred from control region sequences - Jing Zhang; Nan Zhang; Yuan Li; Jiaguang Xiao; Ran Zhang; Tianxiang Gao; Longshan Lin (Marine Biodiversity, 2019)

QTL Mapping for Red Blotches in Malaysia Red Tilapia (Oreochromis spp.) - Bi Jun Li; Zong Xian Zhu; Xiao Hui Gu; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

Identifying a Long QTL Cluster Across chrLG18 Associated with Salt Tolerance in Tilapia Using GWAS and QTL-seq - Dan Li Jiang; Xiao Hui Gu; Bi Jun Li; Zong Xian Zhu; Hui Qin; Zi ning Meng; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

A life support-based comprehensive treatment regimen dramatically lowers the in-hospital mortality of patients with fulminant myocarditis: a multiple center study - Sheng Li; Shengyong Xu; Chenze Li; Xiao Ran; Guanglin Cui; Mengying He; Kun Miao; Chunxia Zhao; Jiangtao Yan; Rutai Hui; Ning Zhou; Yan Wang; et al. (Science China Life Sciences, 2019)

Bituminous coal combustion and Xuan Wei Lung cancer: a review of the epidemiology, intervention, carcinogens, and carcinogenesis - Jinhui Li; Jinjun Ran; Lung-chi Chen; Max Costa; Yunchao Huang; Xiao Chen; Linwei Tian (Archives of Toxicology, 2019)

The research progress in mechanism and influence of biosorption between lactic acid bacteria and Pb(II): A review - Derong Lin; Ran Ji; Dan Wang; Mengshi Xiao; Jingjing Zhao; Jinpeng Zou; Yutong Li; Tao Qin; Baoshan Xing; Yuan Chen; Peng Liu; Zhijun Wu; et al. (Critical Reviews in Food Science and Nutrition, 2019)

Early Hemolysis Within Human Intracerebral Hematomas: an MRI Study - Ran Liu; Haijiao Li; Ya Hua; Richard F. Keep; Jiangxi Xiao; Guohua Xi; Yining Huang (Translational Stroke Research, 2019)

Quantitative Structure-Property Relationship for pH-Triggered Drug Release Performance of Acid-Responsive Four/Six-Arms Star Polymeric Micelles - Ran Zhang; Li-yang Wen; Wen-sheng Wu; Xiao-zhe Yuan; Li-juan Zhang (Pharmaceutical Research, 2019)

Identification of drug target candidates of the swine pathogen Actinobacillus pleuropneumoniae by construction of protein–protein interaction network - Siqi Li; Zhipeng Su; Chengjun Zhang; Zhuofei Xu; Xiaoping Chang; Jiawen Zhu; Ran Xiao; Lu Li; Rui Zhou (Genes & Genomics, 2018)

Genetic mapping and salt tolerance of a novel D1-allelic mutant of rice (Oryza sativa L.) - Wei-jiang Tian; Xiao-qiong Zhang; Xiao-wen Wang; Jia Xie; Yang-yang Li; Ying Sun; Yi-ran Tao; Yu-zhen Xiong; Xian-chun Sang (Acta Physiologiae Plantarum, 2018)

A guanine insert in OsBBS1 leads to early leaf senescence and salt stress sensitivity in rice (Oryza sativa L.) - Dong-Dong Zeng; Cheng-Cong Yang; Ran Qin; Md. Alamin; Er-Kui Yue; Xiao-Li Jin; Chun-Hai Shi (Plant Cell Reports, 2018)

Identifying a Major QTL Associated with Salinity Tolerance in Nile Tilapia Using QTL-Seq - Xiao Hui Gu; Dan Li Jiang; Yan Huang; Bi Jun Li; Chao Hao Chen; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2018)

Characterization and Fine Mapping of SFL1, a Gene Controlling Screw Flag Leaf in Rice - Md. Alamin; Dong-Dong Zeng; Ran Qin; Most. Humaira Sultana; Xiao-Li Jin; Chun-Hai Shi (Plant Molecular Biology Reporter, 2017)

Genome-Wide QTL Analysis Identified Significant Associations Between Hypoxia Tolerance and Mutations in the GPR132 and ABCG4 Genes in Nile Tilapia - Hong Lian Li; Xiao Hui Gu; Bi Jun Li; Chao Hao Chen; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

The ferredoxin-dependent glutamate synthase (OsFd-GOGAT) participates in leaf senescence and the nitrogen remobilization in rice - Dong-Dong Zeng; Ran Qin; Mei Li; Md. Alamin; Xiao-Li Jin; Yu Liu; Chun-Hai Shi (Molecular Genetics and Genomics, 2017)

DBOP specifies palea development by suppressing the expansion of the margin of palea in rice - Dong-Dong Zeng; Ran Qin; Md. Alamin; Rong Liang; Cheng-Cong Yang; Xiao-Li Jin; Chun-Hai Shi (Genes & Genomics, 2016)

Expression, secretion and bactericidal activity of type VI secretion system in Vibrio anguillarum - Lei Tang; Shu Yue; Gui-Yang Li; Jie Li; Xiao-Ran Wang; Shu-Fang Li; Zhao-Lan Mo (Archives of Microbiology, 2016)

Directed differentiation of human embryonic stem cells into keratinocyte progenitors in vitro: an attempt with promise of clinical use - Hanqing Li; Haiwen Zhou; Xin Fu; Ran Xiao (In Vitro Cellular & Developmental Biology - Animal, 2016)

Complete genome sequence and comparative genome analysis of a new special Yersinia enterocolitica - Guoxiang Shi; Mingming Su; Junrong Liang; Ran Duan; Wenpeng Gu; Yuchun Xiao; Zhewen Zhang; Haiyan Qiu; Zheng Zhang; Yi Li; Xiaohe Zhang; Yunchao Ling; et al. (Archives of Microbiology, 2016)

Follicle-stimulating hormone increases the intramuscular fat content and expression of lipid biosynthesis genes in chicken breast muscle - Xiao-yan Cui; Ying-ying Li; Ran-ran Liu; Gui-ping Zhao; Mai-qing Zheng; Qing-he Li; Jie Wen (Journal of Zhejiang University-SCIENCE B, 2016)

The SIRT1 inhibitor, nicotinamide, inhibits hepatitis B virus replication in vitro and in vivo - Wan-Yu Li; Ji-Hua Ren; Na-Na Tao; Long-Kuan Ran; Xiang Chen; Hong-Zhong Zhou; Bo Liu; Xiao-Song Li; Ai-Long Huang; Juan Chen (Archives of Virology, 2016)

A high frequency of allopolyploid speciation in the gymnospermous genus E phedra and its possible association with some biological and ecological features - Hui Wu; Zhen Ma; Ming‐Ming Wang; Ai‐Li Qin; Jin‐Hua Ran; Xiao‐Quan Wang (Molecular Ecology, 2016)
The origin and evolution of polyploids have been studied extensively in angiosperms and ferns but very rarely in gymnosperms. With the exception of three species of conifers, all natural polyploid species of gymnosperms belong to Ephedra , in which more than half of the species show polyploid cytotypes. Here, we investigated the origin and evolution of polyploids of Ephedra distributed in the Qinghai–Tibetan Plateau ( QTP ) and neighbouring areas. Flow cytometry ( FCM ) was used to measure the ploidy levels of the sampled species that are represented by multiple individuals from different populations, and then, two single‐copy nuclear genes ( LFY and DDB 2) and two chloroplast DNA fragments were used to unravel the possible origins and maternal donors of the polyploids. The results indicate that the studied polyploid species are allopolyploids, and suggest that allotetraploidy is a dominant mode of speciation in Ephedra . The high percentage of polyploids in the genus could be related to some of its biological attributes such as vegetative propagation, a relatively high rate of unreduced gamete formation, and a small genome size relative to most other gymnosperms. Significant ecological divergences between allotetraploids and their putative progenitors were detected by PCA s and anova and Tukey's tests, with the exception of E. saxatilis . The overlap of geographical distributions and ecological niches of some diploid species could have provided opportunities for interspecific hybridization and allopolyploid speciation.

Procalcitonin levels in patients with positive blood culture, positive body fluid culture, sepsis, and severe sepsis: a cross-sectional study - Ying Yu; Xia-Xi Li; Ling-Xiao Jiang; Meng Du; Zhan-Guo Liu; Zhong-Ran Cen; Hua Wang; Zhen-Hui Guo; Ping Chang (Infectious Diseases, 2016)

PPR protein PDM1/SEL1 is involved in RNA editing and splicing of plastid genes in Arabidopsis thaliana - Hong-Dao Zhang; Yong-Lan Cui; Chao Huang; Qian-Qian Yin; Xue-Mei Qin; Te Xu; Xiao-Fang He; Yi Zhang; Zi-Ran Li; Zhong-Nan Yang (Photosynthesis Research, 2015)

Odontoblast β-catenin signaling regulates fenestration of mouse Hertwig’s epithelial root sheath - Ran Zhang; Yan Teng; Liang Zhu; JingTing Lin; Xiao Yang; Guan Yang; TieJun Li (Science China Life Sciences, 2015)

Comparison of changes in land use and land cover in China and the USA over the past 300 years - Fanneng He; Meijiao Li; Shicheng Li; Ran Xiao (Journal of Geographical Sciences, 2015)

Changes in root morphology and physiology to limited phosphorus and moisture in a locally-selected cultivar and an introduced cultivar of Medicago sativa L. growing in alkaline soil - Jing-Wei Fan; Yan-Lei Du; Neil C. Turner; Bing-Ru Wang; Yan Fang; Yue Xi; Xiao-Ran Guo; Feng-Min Li (Plant and Soil, 2015)

Generation of bi-transgenic pigs overexpressing human lactoferrin and lysozyme in milk - Dan Cui; Jia Li; Linlin Zhang; Shen Liu; Xiao Wen; Qiuyan Li; Yaofeng Zhao; Xiaoxiang Hu; Ran Zhang; Ning Li (Transgenic Research, 2015)

A theoretical analysis of basin-scale groundwater temperature distribution - Ran An; Xiao-Wei Jiang; Jun-Zhi Wang; Li Wan; Xu-Sheng Wang; Hailong Li (Hydrogeology Journal, 2015)

Retrospective Review on Obstetric Cases of Critically Ill and Dead Patients in Dongguan - Li-Han Shen; Yun-Yong Fang; Yan-Bing Zheng; Li-Juan Xiao; Su-Ran Huang; Xi-Zhen Liu; Li-Hua Cai (Cell Biochemistry and Biophysics, 2015)

A novel species of ellipsoidal multicellular magnetotactic prokaryotes from L ake Y uehu in C hina - Yi‐Ran Chen; Rui Zhang; Hai‐Jian Du; Hong‐Miao Pan; Wen‐Yan Zhang; Ke Zhou; Jin‐Hua Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2015)
Summary Two morphotypes of multicellular magnetotactic prokaryotes ( MMPs ) have been identified: spherical (several species) and ellipsoidal (previously one species). Here, we report novel ellipsoidal MMPs that are ∼ 10 × 8 μm in size, and composed of about 86 cells arranged in six to eight interlaced circles. Each MMP was composed of cells that synthesized either bullet‐shaped magnetite magnetosomes alone, or both bullet‐shaped magnetite and rectangular greigite magnetosomes. They showed north‐seeking magnetotaxis, ping‐pong motility and negative phototaxis at a velocity up to 300 μm s −1 . During reproduction, they divided along either their long‐ or short‐body axes. For genetic analysis, we sorted the ellipsoidal MMPs with micromanipulation and amplified their genomes using multiple displacement amplification. We sequenced the 16 S r RNA gene and found 6.9% sequence divergence from that of ellipsoidal MMPs , Candidatus Magnetananas tsingtaoensis and > 8.3% divergence from those of spherical MMPs . Therefore, the novel MMPs belong to different species and genus compared with the currently known ellipsoidal and spherical MMPs respectively. The novel MMPs display a morphological cell differentiation, implying a potential division of labour. These findings provide new insights into the diversity of MMPs in general, and contribute to our understanding of the evolution of multicellularity among prokaryotes.

Determination of royal jelly freshness by ELISA with a highly specific anti-apalbumin 1, major royal jelly protein 1 antibody - Li-rong Shen; Yi-ran Wang; Liang Zhai; Wen-xiu Zhou; Liang-liang Tan; Mei-lu Li; Dan-dan Liu; Fa Xiao (Journal of Zhejiang University-SCIENCE B, 2015)

Recycling of sediment into the mantle source of K-rich mafic rocks: Sr–Nd–Hf–O isotopic evidence from the Fushui complex in the Qinling orogen - Hao Wang; Yuan-Bao Wu; Chao-Ran Li; Tian-Yu Zhao; Zheng-Wei Qin; Liu-Qin Zhu; Shan Gao; Jian-Ping Zheng; Xiao-Ming Liu; Lian Zhou; Yang Zhang; Sai-Hong Yang (Contributions to Mineralogy and Petrology, 2014)

Analysis of quality factors for Rayleigh channel waves - Xiao-Hui Yang; Si-Yuan Cao; De-Chun Li; Peng-Fei Yu; Hao-Ran Zhang (Applied Geophysics, 2014)

A new oleanane-type triterpenoidal saponin from Pulsatilla chinensis - Zhan Shu; Zhong Chen; Yan-li Liu; Wei-feng Zhu; Yu-lin Feng; Qiong-ming Xu; Xiao-ran Li; Shi-lin Yang (Natural Product Research, 2013)

A chloroplast membrane protein LTO1/AtVKOR involving in redox regulation and ROS homeostasis - Ying Lu; Hua-Rong Wang; Han Li; Hao-Ran Cui; Yue-Guang Feng; Xiao-Yun Wang (Plant Cell Reports, 2013)

Spectroscopic exploring the affinities, characteristics, and mode of binding interaction of curcumin with DNA - Xiao-Ling Li; Yan-Jun Hu; Ran Mi; Xiao-Yun Li; Pei-Qi Li; Yu Ouyang (Molecular Biology Reports, 2013)

Biophysical studies on the interactions of jatrorrhizine with bovine serum albumin by spectroscopic and molecular modeling methods - Ran Mi; Pei-Qi Li; Yan-Jun Hu; Xiao-Yang Fan; Hai-Ying Li; Xue-Cheng Yu; Yu Ouyang (Molecular Biology Reports, 2013)

The Antitumor Effect of a New Docetaxel-Loaded Microbubble Combined with Low-Frequency Ultrasound In Vitro: Preparation and Parameter Analysis - Shu-Ting Ren; Yi-Ran Liao; Xiao-Ning Kang; Yi-Ping Li; Hui Zhang; Hong Ai; Qiang Sun; Jing Jing; Xing-Hua Zhao; Li-Fang Tan; Xin-Liang Shen; Bing Wang (Pharmaceutical Research, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Abundance and composition of ammonia-oxidizing bacteria and archaea in different types of soil in the Yangtze River estuary - Xiao-ran Li; Yi-ping Xiao; Wen-wei Ren; Zeng-fu Liu; Jin-huan Shi; Zhe-xue Quan (Journal of Zhejiang University-SCIENCE B, 2012)

Natural populations of lactic acid bacteria in douchi from Yunnan Province, China - Chen-jian Liu; Fu-ming Gong; Xiao-ran Li; Hai-yan Li; Zhong-hua Zhang; Yue Feng; Hiroko Nagano (Journal of Zhejiang University-SCIENCE B, 2012)

Polymorphisms of KiSS-1 and GPR54 genes and their relationships with litter size in sheep - Mingxing Chu; Chaoting Xiao; Tao Feng; Yan Fu; Guiling Cao; Li Fang; Ran Di; Qianqian Tang; Dongwei Huang; Yuehui Ma; Kui Li; Ning Li (Molecular Biology Reports, 2012)

Growth rate, catalase and superoxide dismutase activities in rock carp (Procypris rabaudi Tchang) exposed to supersaturated total dissolved gas - Xiao-qing Liu; Ke-feng Li; Jun Du; Jia Li; Ran Li (Journal of Zhejiang University-SCIENCE B, 2011)

Expressions of thermostable bacterial cellulases in tobacco plant - Xi-ran Jiang; Xiao-ya Zhou; Wen-yan Jiang; Xiao-rong Gao; Wen-li Li (Biotechnology Letters, 2011)

Three new fatty acids from the roots of Boehmeria nivea (L.) Gaudich and their antifungal activities - Qiong-Ming Xu; Yan-Li Liu; Xiao-Ran Li; Xia Li; Shi-Lin Yang (Natural Product Research, 2011)

Could nested PCR be applicable for the study of microbial diversity? - Zhen-Yu Fan; Xiao-Ran Li; Dan-Ping Mao; Gen-Feng Zhu; Sheng-Yue Wang; Zhe-Xue Quan (World Journal of Microbiology and Biotechnology, 2009)

Analysis of Prevalence and Risk Factors of Hypertension Among Uygur Adults in Tushala and Hetian Xinjiang Uygur Autonomous Region - Lin-Lin Li; Xiao-Yan Liu; Jian-Xin Ran; Ye Wang; Xin Luo; Tao Wang; Jun Ren; Mayinuer Aisha; Rebiya Abudureheman; Adalaiti Xiawudong; Xiao-Chun Zhang; Xin-Min Mao (Cardiovascular Toxicology, 2008)

Effect of different dietary raw to pre-gelatinized starch ratios on growth performance, feed utilization and body composition of juvenile yellowfin seabream (Sparus latus) - Xiao-Yi Wu; Yong-Jian Liu; Li-Xia Tian; Kang-Sen Mai; Ran Guo; Sheng-Jie Jin (Aquaculture International, 2007)

Rapid Evolution, Genetic Variations, and Functional Association of the Human Spermatogenesis-Related Gene NYD-SP12 - Qü Zhang; Feng Zhang; Xiao-hua Chen; Yin-qiu Wang; Wei-qi Wang; Alice A. Lin; Luca L. Cavalli-Sforza; Li Jin; Ran Huo; Jia-hao Sha; Zheng Li; Bing Su (Journal of Molecular Evolution, 2007)

Effects of aromatizable and nonaromatizable androgens on the sex inversion of red-spotted grouper (Epinephelus akaara) - Guang-Li Li; Xiao-Chun Liu; Hao-Ran Lin (Fish Physiology and Biochemistry, 2006)